Complex tungsten oxide particle, near infrared absorbing particle dispersed liquid, and near infrared absorbing particle dispersion

Composite tungsten oxide particles with a hexagonal structure and controlled synthesis process address the limitations of existing particles by enhancing visible light transmission and infrared shielding, achieving improved transmittance and color neutrality.

JP2025006005APending Publication Date: 2025-01-17SUMITOMO METAL MINING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023106511
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing composite tungsten oxide particles for near-infrared shielding have limitations in visible light transmission and infrared shielding performance, particularly exhibiting a sudden decrease in transmittance at wavelengths around 700-800 nm, leading to undesirable color tones and reduced transparency.

Method used

The development of composite tungsten oxide particles with a hexagonal crystal structure, specific elemental composition (M x W y O z ), controlled particle size (800 nm or less), and uniform particle distribution, achieved through a method involving aerosol formation, heat treatment, and reduction treatment, to enhance visible light transmission and infrared shielding.

Benefits of technology

The composite tungsten oxide particles exhibit improved visible light transmission with transmittance of 75% or more at 600 nm and 20% or more at 800 nm, while maintaining effective infrared shielding, resulting in a more neutral color tone and enhanced transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006005000001_ABST
    Figure 2025006005000001_ABST
Patent Text Reader

Abstract

To provide a complex tungsten oxide particle which has excellent visible light transmission performance and infrared light shielding performance and enables a light transmittance of 20% or more at a wavelength of 800 nm when the light transmittance at a wavelength of 600 nm is 75% or more.SOLUTION: A complex tungsten oxide particle contains a complex tungsten oxide. The complex tungsten oxide is represented by the general formula MxWyOz (0.20≤x / y≤0.37 and 2.2≤z / y≤3.3) and has a hexagonal crystal system. An STEM-HAADF image with [001] incidence of the complex tungsten oxide particle has spots where the Z contrast of tungsten atoms is reduced to 95% or less of the average value, at a number percentage of 0.01% or more and 10% or less. The complex tungsten oxide particle has a variation coefficient obtained by dividing a standard deviation for a number-based particle size distribution by a number-based average particle diameter of 0.2 or less.SELECTED DRAWING: Figure 9
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite tungsten oxide particles, a near infrared absorbing particle dispersion, and a near infrared absorbing particle dispersion. [Background technology]

[0002] Various near-infrared shielding technologies have been proposed to reduce solar radiation transmittance while maintaining good visible light transmittance and transparency. Among them, near-infrared shielding technologies using inorganic conductive fine particles have the advantages of superior near-infrared shielding properties compared to other technologies, low cost, radio wave transmittance, and high weather resistance.

[0003] For example, in Patent Document 1, the general formula M x W y O z (wherein M is one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, and I; W is tungsten; O is oxygen; and 0.001≦x / y≦1, 2.2≦z / y≦3.0) is dispersed as infrared-shielding material microparticles in a medium such as a resin; and a technique relating to a manufacturing method of the infrared-shielding material microparticles is disclosed. Patent Document 1 also discloses an example of producing an infrared shielding film that is a thin-film dispersion of fine particles of an infrared shielding material.

[0004] According to Patent Document 1, it is possible to prepare an infrared-shielding material microparticle dispersion having excellent optical properties, such as more efficient shielding of sunlight, particularly light in the near-infrared region, while at the same time maintaining transmittance in the visible light region, etc. For this reason, application of the infrared-shielding particle dispersion disclosed in Patent Document 1 to various applications such as window glass has been considered.

[0005] Meanwhile, various studies have been conducted on methods for producing composite tungsten oxide particles useful as a near-infrared shielding material.

[0006] For example, the inventor of Patent Document 1 described in Non-Patent Document 1 that Cs 0.32 proposed a method for synthesizing WO3 nanoparticles. However, the particle size in the synthesis method disclosed in Non-Patent Document 1 was large, and a pulverization process was required to produce nanoparticles. This could increase the number of process steps.

[0007] Patent Document 2 proposes the synthesis of potassium-cesium-tungsten bronze solid solution particles using a plasma torch under a reducing atmosphere.

[0008] Non-Patent Document 2 describes Cs by hydrothermal synthesis. x A method for synthesizing WO3 has been disclosed. However, the hydrothermal synthesis method requires a synthesis time of several tens of hours or more. In addition, the hydrothermal synthesis method has a problem in that it requires a large number of steps, such as post-treatment steps.

[0009] Non-Patent Document 3 discloses a synthesis method based on inductively coupled thermal plasma technology. However, this synthesis method requires the introduction of an inductively coupled thermal plasma device, which increases the introduction and running costs.

[0010] Non-Patent Document 4 discloses a method for synthesizing a composite tungsten oxide by a water-solvent flame spray pyrolysis method. However, the infrared absorption characteristics were poor because the amount of Cs was small.

[0011] Non-Patent Document 5 discloses a method for synthesizing a composite tungsten oxide by a water-solvent spray pyrolysis method, which produces a composite tungsten oxide with little Cs desorption from the particle surface. However, the infrared absorption properties were poor.

[0012] Patent Documents 3 and 4 disclose methods for producing composite tungsten microparticles by flame spraying.

Prior Art Documents

Patent Documents

[0013]

Patent Document 1

Patent Document 2

Patent Document 3

Patent Document 4

Non - Patent Documents

[0014]

Non - Patent Document 1

Non - Patent Document 2

Non - Patent Document 3

[0015] As described above, the composite tungsten oxide particles are useful as a near-infrared shielding material. However, there is a demand for a material that has better visible light transmission performance and improved infrared shielding performance than the conventionally known composite tungsten oxide particles.

[0016] In addition, the composite tungsten oxide disclosed in Patent Document 1 may experience a rapid drop in transmittance in the wavelength range of 700 nm to 800 nm, and therefore may have a bluish hue that cannot be considered neutral because it blocks red light. Therefore, a material with excellent transmittance at a wavelength of 800 nm is also required.

[0017] Therefore, one aspect of the present invention aims to provide composite tungsten oxide particles that have excellent visible light transmission performance and infrared shielding performance, and can achieve a transmittance of 20% or more for light with a wavelength of 800 nm when the transmittance of light with a wavelength of 600 nm is 75% or more. [Means for solving the problem]

[0018] In one aspect of the present invention, there is provided a composite tungsten oxide particle comprising a composite tungsten oxide, The composite tungsten oxide is General formula M x W y O z (wherein M element is one or more elements selected from alkali metal elements, alkaline earth metal elements, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, and I; W is tungsten; O is oxygen; 0.20≦x / y≦0.37, 2.2≦z / y≦3.3), The crystal system is hexagonal, In a STEM-HAADF image of the composite tungsten oxide particle from

[0001] incidence, the number of spots in which the Z contrast of tungsten atoms has fallen to 95% or less of the average value is 0.01% or more and 10% or less, The present invention provides composite tungsten oxide particles having a coefficient of variation, calculated by dividing the standard deviation of the particle size distribution based on the number of particles by the average particle size based on the number of particles, of 0.2 or less. Effect of the Invention

[0019] One aspect of the present invention provides composite tungsten oxide particles that have excellent visible light transmission performance and infrared shielding performance, and can achieve a light transmittance of 20% or more at a wavelength of 800 nm when the light transmittance at a wavelength of 600 nm is 75% or more. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a schematic diagram of a composite material production apparatus that can be suitably used in the method for producing composite tungsten oxide particles of this embodiment. [Diagram 2] FIG. 2 is an explanatory diagram of the reduction treatment device used in the reduction treatment step. [Diagram 3] FIG. 3 is a schematic diagram of a near infrared absorbing particle dispersion liquid. [Figure 4] FIG. 4 is a schematic diagram of a near infrared absorbing particle dispersion. [Diagram 5] FIG. 5 is a schematic diagram of a near-infrared absorbing laminate. [Figure 6] FIG. 6 is a schematic diagram of a near-infrared absorbing transparent substrate. [Figure 7] FIG. 7 is a schematic diagram of the crystal structure of composite tungsten bronze observed at

[0001] incidence. [Figure 8] FIG. 8 is an XRD pattern of the composite tungsten oxide particles obtained in Example 1. [Figure 9] FIG. 9 is a STEM-HAADF image of the composite tungsten oxide particles obtained in Example 1. [Figure 10] FIG. 10 is a line profile quantifying the Z contrast of tungsten atoms in lines L1 to L6 in FIG. [Figure 11] FIG. 11 is a STEM-HAADF image of the composite tungsten oxide particles obtained in Comparative Example 1. [Figure 12] FIG. 12 shows a STEM-HAADF image of the composite tungsten oxide particle obtained in Comparative Example 1, and a line profile quantifying the Z contrast of tungsten atoms. [Figure 13]FIG. 13 shows transmitted light profiles of the near infrared absorbing particle dispersions according to Example 1, Example 2, Example 3, and Comparative Example 1. [Figure 14] FIG. 14 is a transmission electron microscope image of the near infrared absorbing particles contained in the near infrared absorbing particle dispersion liquids according to Example 1, Example 2, Example 3, and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Specific examples of composite tungsten oxide particles, near infrared absorbing particle dispersion liquid, and near infrared absorbing particle dispersion according to one embodiment of the present disclosure (hereinafter referred to as "present embodiment") will be described below with reference to the drawings. Note that the present invention is not limited to these examples, but is indicated by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims. [Composite tungsten oxide particles] The composite tungsten oxide particles of the present embodiment contain composite tungsten oxide. Note that, the composite tungsten oxide particles may be composed of composite tungsten oxide, but even in this case, it does not exclude the inclusion of inevitable impurities.

[0022] The composite tungsten oxide is represented by the general formula M x W y O z It is expressed as:

[0023] The element M in the above general formula can be one or more elements selected from alkali metal elements, alkaline earth metal elements, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, and I. In addition, W represents tungsten, O represents oxygen, and x, y, and z preferably satisfy 0.20≦x / y≦0.37 and 2.2≦z / y≦3.3, respectively.

[0024] Examples of the alkali metal elements include Li, Na, K, Rb, Cs, and Fr. Examples of the alkaline earth metal elements include Ca, Sr, Ba, and Ra. Examples of the rare earth elements include Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.

[0025] The composite tungsten oxide has a hexagonal crystal system.

[0026] The composite tungsten oxide particles contain, in a STEM-HAADF image of the composite tungsten oxide particles from

[0001] incidence, spots in which the Z contrast of tungsten atoms has dropped to 95% or less of the average value, in a ratio of 0.01% or more and 10% or less by number. (1) Composition The composite tungsten oxide contained in the composite tungsten oxide particles is represented by the general formula M x W y O z The M element, W, O, and x, y, and z in the formula have already been described, so their explanation will be omitted here.

[0027] The composite tungsten oxide can have one or more tungsten bronze type crystal structures selected from, for example, a tetragonal crystal structure, a cubic crystal structure, and a hexagonal crystal structure. The composite tungsten oxide contained in the composite tungsten oxide particles of this embodiment has a hexagonal crystal structure.

[0028] When the composite tungsten oxide has a hexagonal crystal structure, the particles have improved light transmittance in the visible light region and improved light absorption in the near-infrared region.

[0029] When the composite tungsten oxide has a tetragonal or cubic tungsten bronze type crystal structure, it also functions as an infrared shielding material. However, the absorption position of light in the near infrared region tends to change depending on the crystal structure of the composite tungsten oxide. The absorption position of light in the near infrared region tends to move to the longer wavelength side in the tetragonal crystal than in the cubic crystal, and further to the longer wavelength side in the hexagonal crystal than in the tetragonal crystal. In addition, accompanying the change in the absorption position, the absorption of light in the visible light region is the least in the hexagonal crystal, followed by the tetragonal crystal, and among these, the cubic crystal has the greatest absorption of light in the visible light region. Therefore, for applications in which more light in the visible light region is transmitted and more light in the infrared region is shielded, it is preferable to use a composite tungsten oxide having a hexagonal tungsten bronze type crystal structure.

[0030] As described above, when the composite tungsten oxide has a hexagonal crystal structure, the transmittance of the composite tungsten oxide particles in the visible light region and the absorption of the light in the near infrared region are particularly improved. Therefore, the composite tungsten oxide particles preferably contain a composite tungsten oxide with a hexagonal crystal structure. And, when one or more elements selected from Cs, Rb, K, Tl, Ba, and In are used as the M element, it becomes easy to form a hexagonal crystal. Therefore, the M element preferably contains one or more elements selected from Cs, Rb, K, Tl, Ba, and In, and it is more preferable that the M element contains one or more elements selected from Rb and Cs.

[0031] Here, the arrangement of the M element when the composite tungsten oxide has a hexagonal crystal structure will be described.

[0032] A hexagonal void (tunnel) made of O atoms is formed by assembling six octahedra each consisting of a W (tungsten) atom and six O (oxygen) atoms, that is, an octahedron with an O atom at each apex and a W atom in the center. An M element is placed in the void to form one unit, and many of these units are assembled to form a hexagonal crystal structure.

[0033] When a composite tungsten oxide having a hexagonal crystal structure has a uniform crystal structure, the ratio of the amount of substance of the M element to W is 0.20≦x / y≦0.37, and preferably 0.30≦x / y≦0.36. In theory, when z / y=3, the value of x / y is 0.33, and it is considered that the M element is arranged in all of the hexagonal gaps. Note that the above x, y, and z are the same as those in the general formula M x W y O z means x, y, and z in, and so on.

[0034] The composite tungsten oxide has a composition in which an M element is added to tungsten trioxide (WO3). Since tungsten trioxide does not contain effective free electrons, the ratio of oxygen to 1 mole of tungsten must be less than 3 in order to achieve infrared absorption. However, in the composite tungsten oxide, free electrons are generated by adding an M element, and the infrared absorption effect can be obtained. Therefore, the ratio of oxygen to 1 mole of tungsten can be 3 or less. In addition, the ratio of oxygen to 1 mole of tungsten may exceed 3. However, the crystal phase of WO2 may absorb or scatter light in the visible light region, which may reduce the absorption of light in the near infrared region. Therefore, from the viewpoint of suppressing the generation of WO2, it is preferable that the ratio of oxygen to 1 mole of tungsten is greater than 2.

[0035] Therefore, it is preferable that z / y, which is the ratio of oxygen to 1 mole of tungsten, satisfies 2.2≦z / y≦3.3 as described above. (2) Average particle size When the composite tungsten oxide particle of the present embodiment is used for an application that requires maintaining transparency, the composite tungsten oxide particle preferably has an average particle diameter of 800 nm or less.This is because particles with an average particle diameter of 800 nm or less do not completely block light due to scattering, and can maintain high visibility in the visible light region and efficiently maintain transparency at the same time.In particular, when transparency in the visible light region is important, it is preferable to further consider scattering by particles.

[0036] When emphasis is placed on reducing scattering due to such particles, the average particle size is more preferably 200 nm or less, and even more preferably 100 nm or less.

[0037] This is because if the average particle size is small, the scattering of light in the visible light region due to geometric scattering or Mie scattering is reduced, and the infrared shielding film of the near-infrared absorbing particle dispersion or the like becomes like cloudy glass, and clear transparency can be avoided. And, when the average particle size is 200 nm or less, the geometric scattering or Mie scattering is reduced, and the Rayleigh scattering region is reached. In the Rayleigh scattering region, the scattered light is reduced in proportion to the sixth power of the average particle size, so that the scattering is reduced with the decrease in the average particle size, and the transparency is improved. Furthermore, when the average particle size is 100 nm or less, the scattered light is very small, which is preferable. From the viewpoint of avoiding light scattering, it is preferable that the average particle size is small.

[0038] Therefore, when the composite tungsten oxide particle of this embodiment is required to maintain high visibility in the visible light region as described above, the average particle size is preferably 800nm ​​or less, more preferably 200nm or less, and even more preferably 100nm or less.The lower limit of the average particle size of the composite tungsten oxide particle of this embodiment is not particularly limited, but is preferably 1nm or more, and more preferably 5nm or more.

[0039] The average particle size of the composite tungsten oxide particles is calculated by measuring the particle size of each composite tungsten oxide particle from a transmission electron microscope image. Specifically, three fields of view are selected at a magnification that includes 200 or more composite tungsten oxide particles in each field of view, the images of the composite tungsten oxide particles in each field of view are binarized, and the average particle size is calculated by image analysis.

[0040] The average particle size of the composite tungsten oxide particles can be calculated by the following procedure.

[0041] First, the area of ​​each composite tungsten oxide particle is calculated for all composite tungsten oxide particles contained in three fields of view in a transmission electron microscope image.

[0042] Next, the circle equivalent diameter, that is, the diameter when each composite tungsten oxide particle is regarded as a circle, is calculated from the area of ​​each composite tungsten oxide particle. The calculated circle equivalent diameter can then be regarded as the particle size of each composite tungsten oxide particle.

[0043] After determining the particle size of each composite tungsten oxide particle, i.e., the equivalent circle diameter, the particle sizes of all the composite tungsten oxide particles evaluated are added together, and then divided by the number of particles evaluated, to calculate the average particle size of the composite tungsten oxide particles. That is, the average value of the particle sizes of the composite tungsten oxide particles evaluated can be regarded as the average particle size of the composite tungsten oxide particles.

[0044] In this specification, unless otherwise specified, the average particle size and the median size refer to the number-based average particle size and the number-based median size.

[0045] Furthermore, the composite tungsten oxide particles of this embodiment preferably have a small standard deviation of the particle size distribution based on number.The composite tungsten oxide particles of this embodiment can have a coefficient of variation of 0.2 or less, which is calculated by dividing the standard deviation of the particle size distribution based on number by the average particle size based on number.The coefficient of variation of the composite tungsten oxide particles of this embodiment is preferably 0.16 or less, and more preferably 0.15 or less.

[0046] The coefficient of variation of the composite tungsten oxide particles of this embodiment can be greater than 0, but from the viewpoint of increasing productivity, it is preferably 0.05 or more, and more preferably 0.10 or more.

[0047] Regarding the composite tungsten oxide particles of this embodiment, the coefficient of variation obtained by dividing the standard deviation of the particle size distribution based on number by the average particle size based on number is small, which means that the particle size distribution of the composite tungsten oxide particles is uniform. Also, regarding the composite tungsten oxide particles of this embodiment, the coefficient of variation is small, which means that the transmittance is particularly desirable at each wavelength. (3) Atomic number (Z) contrast of tungsten atoms in composite tungsten oxide particles In the composite tungsten oxide particle of this embodiment, in a STEM-HAADF image (STEM-High-Angle Annular Dark Field) from

[0001] incidence, the number of dark areas in the atomic number (Z) contrast of tungsten atoms (hereinafter also referred to as "Z contrast") is preferably 0.01% or more and 10% or less, more preferably 0.1% or more and 10% or less, and even more preferably 0.2% or more and 10% or less.

[0048] According to the investigations of the inventors of the present invention, the composite tungsten oxide particles can particularly improve the visible light transmission performance and the infrared shielding performance by having a moderate amount of minute oxygen vacancies that are difficult to grasp by XRD patterns, etc.

[0049] And, by the composite tungsten oxide particle containing 10% or less of dark areas in the Z contrast of tungsten atoms (hereinafter also referred to as "W atoms"), the W remaining around the W deficiency region can be oxidized and the amount of oxygen deficiency can be contained to a degree that is not excessive. Also, by the composite tungsten oxide particle containing 0.01% or more of dark areas in the Z contrast of W atoms, the oxygen deficiency can be introduced appropriately.

[0050] A dark area in the Z contrast of W atoms in a composite tungsten oxide particle indicates a loss of W atoms. The dark area in the Z contrast of W atoms refers to a spot (point) where the Z contrast of W atoms falls to 95% or less of the reference value, where the average value of the Z contrast of W atoms included in the observation field of the STEM-HAADF image of the composite tungsten oxide particle is taken as the reference value.

[0051] In the STEM-HAADF image, particles of dispersed composite tungsten oxide particles can be observed with

[0001] incidence, and particles of several tens of nm or more in size can be selected. In order to extract the contrast of the W atom spot, the size of the observation field can be set to 20 nm square or more and 50 nm square or less.

[0052] Figure 7 shows the hexagonal Cs 0.33 The relationship between the crystal structure of the (001) plane of WO3 and the W atom / W atomic row (hereinafter, also referred to as "W / W row") is shown in Fig. 9(A) and Fig. 9(B). 0.33 10(A) to 10(F) show the Z-contrast of W atoms in the W atom / W atomic column along lines L1 to L6 shown in FIG. 9(B).

[0053] The spots where the dark areas of the Z contrast of W atoms were confirmed have weak contrast, such as points P1 and P2 in Figure 9(B), and these spots indicate the loss of W atoms. In Figure 9(B), the tips of the arrows labeled P1 and the like indicate the above-mentioned dark points.

[0054] The Z contrast of W atoms can be seen from the image (STEM-HAADF) obtained by detecting only the transmitted electrons with large scattering angles among the electrons that have passed through the sample when the sample is observed with a scanning transmission electron microscope (STEM-HAADF). Here, the magnitude of the scattering angle is proportional to the square of the atomic number (Z), so the contrast becomes brighter for elements with larger atomic numbers. Therefore, contrast due to differences in composition and elements can be obtained. In the case of composite tungsten bronze, it is possible to distinguish M elements such as Cs from W atoms by the difference in contrast.

[0055] In this embodiment, in order to distinguish between a deficiency and a non-deficiency of W atoms, the difference in contrast intensity at a tungsten column (W column), which is a spot (point) where tungsten is arranged, in a STEM-HAADF image is utilized. If W atoms are missing, the maximum value of Z contrast at that spot decreases. For example, hexagonal Cs 0.33 The vacant W atom sites on the (001) surface of WO3 are shown by a contrast lower than the average Z contrast at the spots where W atoms are arranged in the W atom / W atomic column.

[0056] From the process of synthesizing the composite tungsten oxide particles of this embodiment, it will be explained that the Z contrast of W atoms is confirmed in the STEM-HAADF image of the composite tungsten oxide particles from the

[0001] incidence.

[0057] The (001) plane of the hexagonal composite tungsten oxide will be described from the perspective of the crystal structure. As shown in Fig. 7, an octahedron 74 is formed with a W atom 71 and six O atoms 72 as a unit, that is, an octahedron 74 with an O atom at each apex and a W atom 71 at the center is assembled to form a hexagonal void (tunnel) 75 composed of O atoms 72. In Fig. 7, circles with the same hatching indicate the same atom.

[0058] Then, M elements 73 are arranged in hexagonal gaps 75 formed by O atoms 72 to form one unit. Furthermore, a large number of these units are assembled to form a hexagonal crystal structure. The hexagonal gaps 75 are parallel to the (001) plane. The (001) plane is also perpendicular to the c-axis. By observing the (001) plane, it is possible to crystallographically distinguish the difference between M elements 73 and W atoms 71.

[0059] The composite tungsten oxide particles of this embodiment are Cs 0.33 The change in the crystal structure of particles during the synthesis process will be described using WO3 particles as an example. The composite tungsten oxide particles of this embodiment are manufactured through a raw material preparation process, an aerosol formation process, a heat treatment process, and a reduction treatment process, as described below. The raw material aerosolized in the aerosol formation process is rapidly heated to 500°C or higher in the heat treatment process, and a reaction that changes the raw material into composite tungsten oxide by short heating is promoted. After heating, the raw material is rapidly cooled to stop the reaction that changes the raw material into composite tungsten oxide. The composite tungsten oxide particles obtained through the heat treatment process are composed of a hexagonal crystal (Cs 0.33 WO3) and heterophase (Cs4W 11 O 35 , (CsO) 0.44 WO6, etc. STEM-HAADF image observation of composite tungsten oxide particles confirms that they contain a large number of missing W atoms. These missing W atoms become Cs-rich regions and contribute to the formation of a different phase.

[0060] Composite tungsten oxide particles containing heterogeneous phases obtained through the heat treatment process undergo a rearrangement of M elements Cs atoms, W atoms, and O atoms in a reduction process in which oxygen is not supplied. The rearrangement of the atoms changes the particles into composite tungsten oxide particles in which dark areas are observed in the Z contrast of W atoms in STEM-HAADF images from

[0001] incidence. The dark areas in the Z contrast of W atoms in STEM-HAADF images from

[0001] incidence of composite tungsten oxide particles that have undergone the reduction process are presumed to be traces of the above-mentioned heterogeneous phases and missing W atoms.

[0061] On the other hand, as shown in Comparative Example 1 described later, when the raw materials are not aerosolized and the composite tungsten oxide particles are heated in a reducing atmosphere for a longer time than in Example 1, hexagonal single-phase composite tungsten oxide particles can be obtained by adjusting the atmosphere and heating conditions. As shown in Figure 11 (B), which is the evaluation result of Comparative Example 1, the composite tungsten oxide particles prepared without aerosolizing the raw materials hardly show any dark areas in the Z contrast of W atoms even when observing the STEM-HAADF image from

[0001] incidence.

[0062] According to the composite tungsten oxide particles of this embodiment, it is possible to obtain composite tungsten oxide particles that are excellent in visible light transmission performance and infrared shielding performance, and also have excellent transmittance of light with a wavelength of 800 nm.

[0063] The composite tungsten oxide particles of this embodiment can be made into a dispersion liquid dispersed in a solvent or a dispersion body dispersed in a solid medium. The dispersion liquid or dispersion body has an excellent infrared shielding effect, in which the transmittance peak in the wavelength region of 450 nm to 600 nm can be 80% or more, and the transmittance bottom in the near infrared region can be 10% or less. That is, when made into a dispersion liquid or dispersion body, the composite tungsten oxide particles can be made to have excellent visible light transmission performance and infrared shielding performance. Furthermore, the dispersion liquid or dispersion body using the composite tungsten oxide particles of this embodiment can increase the transmittance of red light at a wavelength of around 800 nm compared to the dispersion liquid of the composite tungsten oxide particles shown in Comparative Example 1. Therefore, it can also contribute to improving the color tone of the dispersion liquid or dispersion body using the composite tungsten oxide particles. For example, in the case where the transmittance at a wavelength of 600 nm is 75% or more in the transmitted light profile, the composite tungsten oxide particle of this embodiment can achieve a transmittance of 50% or more at a wavelength of 700 nm, a transmittance of 20% or more at a wavelength of 800 nm, and a transmittance of 15% or less at a wavelength of 1000 nm. The transmittance at a wavelength of 800 nm can be more preferably 25% or more.

[0064] The composite tungsten oxide particles of this embodiment, when made into a dispersion or a dispersion, transmit light of longer wavelengths in the visible light region (wavelengths of 380 nm to 780 nm) more easily than conventional composite tungsten oxide particles, resulting in a more neutral color tone. On the other hand, a transmittance of 15% or less can be achieved at a wavelength of 1000 nm in the near-infrared region, so that infrared shielding can be achieved in the same way as conventional composite tungsten oxide particles.

[0065] In other words, by using the composite tungsten oxide particles of this embodiment, it is possible to obtain a dispersion liquid or dispersion that has a more neutral transmitted color while suppressing the solar transmittance and that can ensure the transmittance of the sensor wavelength. [Method of manufacturing composite tungsten oxide particles] An outline of the method for producing the composite tungsten oxide particles of the present embodiment will be described.

[0066] According to the method for producing composite tungsten oxide particles of the present embodiment, the composite tungsten oxide particles described above can be produced, so the items already described will be omitted. Note that, here, the method for producing composite tungsten oxide particles is merely shown as a configuration example, and the method for producing composite tungsten oxide particles described above is not limited to the following configuration example.

[0067] The method for producing the composite tungsten oxide particles of the present embodiment is preferably a method capable of directly synthesizing composite tungsten oxide particles having a particle size of 1 μm or less. If composite tungsten oxide particles having a particle size of 1 μm or less can be directly synthesized, it is possible to obtain fine particles that are less affected by damage caused by pulverization or dispersion, for example, composite tungsten oxide particles having a particle size of 800 nm or less.

[0068] A preferred method for directly synthesizing composite tungsten oxide particles with a particle size of 1 μm or less is a manufacturing method in which the particles are synthesized through a heat treatment process in which an aerosol of raw material containing an M element source and a tungsten element source is supplied to an electric furnace, flame, or plasma.

[0069] Therefore, the method for producing composite tungsten oxide particles of the present embodiment can have the following raw material preparation step, aerosol formation step, heat treatment step, and reduction treatment step.

[0070] In the raw material preparation step, a raw material containing an M element source and a tungsten element source can be prepared.

[0071] In the aerosol forming step, the raw material prepared in the raw material preparing step can be turned into an aerosol.

[0072] In the heat treatment process, the aerosolized raw material can be heat treated in a reaction field.

[0073] In the reduction treatment step, the particles obtained in the heat treatment step can be reduced in an atmosphere containing a reducing gas. (1) About each process Hereinafter, each step of the method for producing the composite tungsten oxide particles of the present embodiment will be described. (1-1) Raw material preparation process In the raw material preparation step, a raw material containing an M element source and a tungsten element source (hereinafter also referred to as a "W element source") can be prepared.

[0074] In the raw material preparation step, the raw materials can be blended and prepared so that the ratio of the substance amount of the M element to the substance amount of the W element contained in the raw materials corresponds to the composition of the intended composite tungsten oxide particles.

[0075] The state of the raw material prepared in the raw material preparation step is not particularly limited, and may be liquid or powder, and it is preferable that an aerosol can be formed by spraying, etc. Here, the aerosol means a mixture of minute liquid or solid particles suspended in gas and the surrounding gas.

[0076] When the raw material is a liquid, the raw material can be prepared by preparing a solution containing, for example, an M element source and a W element source.

[0077] Alternatively, a solution containing an M element source and a solution containing a W element source may be prepared in advance, and the two solutions may be mixed in the source preparation step to form a source mixed solution.

[0078] For example, the raw material may be supplied in the form of droplets to the heat treatment process described later. In this case, the solution containing the M element source and the solution containing the W element source may be mixed together immediately before being supplied to a droplet forming section (droplet forming means) that forms the droplets, or in the droplet forming section, to carry out the raw material preparation process. Then, the aerosol formation process described later can be carried out in the droplet forming section.

[0079] For example, if a solution containing an M element source and a solution containing a W element source are mixed in advance, causing problems such as gelation, it is preferable to prepare both solutions in advance as described above and mix them just before the aerosol formation step. When the raw material preparation step is performed just before the aerosol formation step, the substance amount ratio of the M element and the W element in the raw material can be adjusted to a desired range by adjusting the concentrations of both solutions and the delivery speeds of both solutions to the droplet formation part.

[0080] As described above, when the raw material preparation step is carried out immediately before the aerosol formation step, the aerosol formation step and the raw material preparation step do not need to be clearly separated, and both steps can be carried out continuously.

[0081] When the solution containing the M element source and the solution containing the W element source are mixed in the raw material preparation step as described above, the specific method for mixing is not particularly limited, and any method can be used.

[0082] The W element source is not particularly limited, and may be any raw material containing tungsten, such as tungsten alone or a tungsten compound. As the W element source, a tungsten salt or the like may be used, and for example, hexacarbonyl tungsten may be preferably used. Hexacarbonyl tungsten may be expressed as W(CO)6. In addition, as the solution containing the W element source, an organic solution containing the W element source may be preferably used because of ease of handling.

[0083] The M element source is not particularly limited, and may be any raw material containing the M element, such as the M element alone or a compound containing the M element. As a solution containing the M element source, for example, a solution of a salt containing the M element can be used. The type of salt of the M element that is the M element source is not particularly limited, and for example, one or more types selected from carbonates, acetates, nitrates, hydroxides, etc. of the M element can be used.

[0084] As the solution containing the M element source, an ethanol solution containing the M element source can be preferably used because of ease of handling.

[0085] For example, even when the M element is cesium, one or more salts selected from carbonates, acetates, nitrates, hydroxides, etc. can be used as the salt of the M element source, but acetates are particularly preferred because cesium acetate is particularly easily dissolved in ethanol.

[0086] The ratio of the M element to 1 mole of tungsten element in the obtained composite tungsten oxide, i.e., the doping amount, is determined by the ratio of the W element source and the M element source when forming the raw material mixed solution. Therefore, it can be controlled by, for example, the concentration of the solution containing the W element source or the concentration of the solution containing the M element source.

[0087] The concentration of the W element source contained in the solution containing the W element source, that is, the concentration of the salt of the W element, is not particularly limited. For example, the tungsten concentration of the solution containing the W element source is preferably 0.001 mol / L or more and 10 mol / L or less, more preferably 0.01 mol / L or more and 10 mol / L or less, and even more preferably 0.01 mol / L or more and 1 mol / L or less. This is because by making the tungsten concentration of the solution containing the W element source 0.001 mol / L or more, the production amount of the composite tungsten oxide particles per unit time can be sufficiently ensured, and for example, a sufficient amount can be recovered by a filter or the like, and productivity can be improved. In addition, by making the tungsten concentration of the solution containing the W element source 10 mol / L or less, the reprecipitation of the dissolved W element source can be suppressed, the generated particles can be suppressed from agglomerating, and for example, the coarse composite tungsten oxide particles having a particle size larger than 1 μm can be suppressed from being mixed in. Furthermore, additives such as a pH adjusting agent and a surfactant can be added to the solution containing the W element source.

[0088] In addition, the concentration of the M element source contained in the solution containing the M element source is not particularly limited, and can be selected depending on the desired composition of the composite tungsten oxide particles to be produced, the concentration of the W element source contained in the solution containing the W element source, etc.

[0089] Any component can be added to the raw material mixture solution in addition to the solution containing the W element source and the solution containing the M element source.

[0090] Up to this point, the case where the raw material is a liquid has been described as an example, but the raw material may be solid, for example, powder. When the raw material is a powder, it can be prepared, for example, by mixing a powder of an M element compound and a powder of a tungsten compound. In addition, for example, a precursor powder obtained by adding a tungsten compound powder to a solution containing an M element source and stirring the mixture, and removing the solvent by drying or the like, can be used as the raw material.

[0091] When the raw material is a solid, the W element source is not particularly limited, and a tungsten salt or the like can be used. For example, H2WO4 or ammonium paratungstate can be preferably used.

[0092] In H2WO4, the elements other than tungsten are H (hydrogen) and O (oxygen), and the elements other than tungsten are discharged outside the system in the heat treatment process described below. Therefore, by using H2WO4 as a W element source, composite tungsten oxide particles can be obtained with reduced impurity contamination, and therefore it is preferably used.

[0093] The source of M element may be, for example, a powder of a salt containing M element. The type of salt containing M element is not particularly limited, but may be, for example, one or more types selected from carbonates, acetates, nitrates, hydroxides, etc. of M element.

[0094] For example, when the M element is cesium, one or more selected from carbonates, acetates, nitrates, hydroxides, etc. can be used, with carbonates being particularly preferred. (1-2) Aerosol formation process In the method for producing composite tungsten oxide particles of this embodiment, it is preferable to supply the raw material prepared in the raw material preparation step in the form of an aerosol to the heat treatment step. Specifically, it is preferable to transport the aerosol by a carrier gas such as oxygen and to subject it to the heat treatment step.

[0095] Therefore, the method for producing composite tungsten oxide particles of the present embodiment can also have an aerosol formation step of converting the raw material into an aerosol containing droplets or particles of the raw material.

[0096] The means and method for forming the aerosol in the aerosol forming step are not particularly limited and can be selected depending on the state of the raw material, etc.

[0097] When the raw material is a liquid, an aerosol can be formed by spraying the raw material liquid toward a carrier gas using various atomizers such as a centrifugal atomizer or a two-fluid nozzle. Also, droplets can be formed by irradiating the liquid with ultrasonic waves.

[0098] When the raw material is a powder, the aerosol can be formed by a device that forms a dispersion state of the raw material powder and supplies the powder into an airflow. For example, the aerosol can be formed by an aerosol forming device that includes a stirring section such as a rotating brush or stirring blade, and a powder supply section including a piston or screw feeder that sends the raw material to the stirring section. The raw material powder supplied from the powder supply section is dispersed into particles that constitute the powder in the stirring section, and an aerosol can be generated from the raw material powder by sending each particle into a carrier gas. The stirring section can select the rotation speed of the brush or stirring blade so that the raw material powder can be dispersed into particles, and it is preferable to rotate it at a high speed.

[0099] When forming droplets dispersed in a gas in the aerosol forming process, the size of the droplets formed is not particularly limited, but the diameter of the droplets is preferably 100 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less. By making the diameter of the droplets 100 μm or less, it is possible to prevent the composite tungsten oxide particles obtained from becoming coarse, and to obtain composite tungsten oxide particles of the nanometer order. The lower limit of the size of the droplets formed in the aerosol forming process is not particularly limited. However, it is difficult to form droplets that are too small, and there is a risk of productivity decreasing, so it is preferable that the size is, for example, 1 μm or more.

[0100] When forming solid particles dispersed in gas in the aerosol forming process, the size of the particles is not particularly limited, but the diameter of the particles is preferably 100 μm or less, more preferably 10 μm or less, and even more preferably 3 μm or less. By making the diameter of the particles 100 μm or less, it is possible to perform heat treatment more reliably to the inside of the particles. The diameter of the particles can be measured in the same manner as the particle diameter of the composite tungsten oxide particles described above. (1-3) Heat treatment process In the heat treatment process, the raw material is heat-treated to process the raw material into composite tungsten oxide particles. The heat treatment may be performed at a temperature of 500°C or higher, and the configuration of the heat source is not particularly limited. For this reason, the heat treatment process can be performed by a method of guiding the raw material into a flame using a carrier gas, a method of guiding the raw material into a tubular electric furnace, a method of guiding the raw material into plasma, or the like. Whether a flame, an electric furnace, or plasma is used, the heat treatment temperature can be 500°C or higher. By performing heat treatment at 500°C or higher, the compounds contained in the raw material are decomposed, and tungsten and the M element react to form a composite tungsten oxide.

[0101] By containing appropriate W atom deficiency or heterophase in the composite tungsten oxide particles obtained after the heat treatment process, composite tungsten oxide particles containing dark areas due to the Z contrast of W atoms can be obtained after the reduction process. Therefore, conditions such as the heat treatment temperature can be selected so that appropriate W atom deficiency or heterophase occurs in the composite tungsten oxide particles obtained after the heat treatment process, and composite tungsten oxide particles in which spots with reduced W atom Z contrast are confirmed are generated after the reduction process. For this reason, it is preferable to perform a preliminary test or the like and select the supply rate of the raw material in the heat treatment process, the heat treatment temperature, etc. so that the desired ratio of dark areas in the Z contrast of W atoms is contained after the reduction process. It is preferable to select conditions such as the heat treatment temperature so that heterophases can be reduced and removed after the reduction process.

[0102] The heat treatment temperature is sufficient to proceed with the reaction between tungsten and the M element, and may be 500° C. or higher, preferably 550° C. or higher, and more preferably 1000° C. or higher. There is no particular upper limit to the heat treatment temperature, but from the viewpoint of suppressing energy consumption, it is preferably 4000° C. or lower.

[0103] In the heat treatment step, a flame can be used as described above, and the raw material can be heat-treated using the flame. By using a flame in the heat treatment step and adjusting the temperature of the flame reaction field, the particle size of the resulting composite tungsten oxide particles can be selected.

[0104] When a liquid raw material is sprayed into a carrier gas to form droplets, and the raw material is introduced into a flame to synthesize composite tungsten oxide particles, the raw material droplets move through the flame by a carrier gas such as oxygen gas. When the raw material droplets are transported into the flame, the organic solvent containing the raw material tungsten source and M element source is burned, and the solvent is decomposed by the combustion reaction. The heat generated by the combustion reaction contributes to the decomposition reaction of tungsten and M element, and precipitates in the process of cooling in the tail flame of the flame field.

[0105] For example, as mentioned above, the W element source can be tungsten hexacarbonyl, and the M element source can be cesium acetate if the M element is cesium, and these salts decompose in the heat treatment process. At this time, W is easily precipitated as WO6, while Cs is difficult to form an oxide as a monomer, and some of it passes through the filter and is discharged to the outside of the system without being precipitated as nano-sized powder.

[0106] In the above case, in the process of decomposing the solute portion, tungsten reacts with the M element to form a composite tungsten oxide.

[0107] When a flame is used in the heat treatment process, the conditions for forming the flame are not particularly limited, but the flame can be formed using, for example, a mixed gas containing oxygen and a hydrocarbon. By forming a flame using a mixed gas containing oxygen and a hydrocarbon, a flame with a stable temperature can be formed, and composite tungsten oxide particles with reduced variation in particle size, etc. can be produced.

[0108] The method of adjusting the size and temperature of the flame is not particularly limited, but it is preferable to adjust the flow rates of the oxygen and the flammable gas such as hydrocarbon in the mixed gas supplied to the flame, while setting the flow rate ratio of both gases so that the flammable gas can be burned. This is because the heat power can be adjusted while ensuring the amount of oxygen necessary for the flammable gas to burn.

[0109] For example, when a flame is formed using a mixed gas containing oxygen and propane, the volume ratio of the flow rates of methane and oxygen (burner) in the mixed gas is preferably 5 to 8 oxygen per 1 propane, and the flow rate of propane is preferably in the range of 0.5 to 2 L / min. This is because, when the flow rate of propane is 1, the combustion of propane, which is a combustible gas, can be sufficiently promoted by setting the flow rate of oxygen to 5 or more. However, it is preferable to supply 8 or less oxygen per 1 propane to avoid excessive supply of oxygen.

[0110] The heat treatment temperature of the flame reaction field etc. also affects the particle size of the resulting composite tungsten oxide particles. Therefore, in order to obtain composite tungsten oxide particles with desired particle size characteristics such as average particle size and variation coefficient, it is preferable to adjust and select the heat treatment conditions in the heat treatment step together with the size of the droplets or particles of the raw material in the aerosol formed in the aerosol formation step.

[0111] This is presumably because thermal energy in a reaction field such as a flame is used to sublimate the generated composite tungsten oxide particles, causing the particles to burst upon sublimation, resulting in particles with fine particle diameters.

[0112] The composite tungsten oxide particles obtained by the heat treatment can be recovered, for example, by using a filter. (1-4) Reduction treatment process Particles obtained through a heat treatment process, specifically composite tungsten oxide particles, may not exhibit infrared absorbing properties.The inventors of the present invention have conducted research and found that the composite tungsten oxide particles obtained through a heat treatment process can exhibit infrared absorbing properties by further carrying out a reduction treatment process for performing a reduction treatment on the composite tungsten oxide particles obtained through the heat treatment process.

[0113] Therefore, the method for producing the composite tungsten oxide particles of this embodiment can also have a reduction treatment step in which the particles obtained in the heat treatment step are reduced under an atmosphere containing a reducing gas.Specifically, for example, the method for producing the composite tungsten oxide particles of this embodiment can have a reduction treatment step in which the particles obtained in the heat treatment step are reduced under an atmosphere containing a reducing gas at a temperature in the range of more than 400°C and less than 700°C after the heat treatment step.

[0114] The conditions of the reduction treatment are not particularly limited, but it is preferable to select the conditions of the reduction treatment so that when the composite tungsten oxide particles after the reduction treatment are analyzed by X-ray diffraction pattern, the crystal structure does not change before and after the reduction treatment process, and metal tungsten does not precipitate. It is also preferable to select the conditions of the reduction treatment so that the composite tungsten oxide particles after the reduction treatment process contain dark areas in the Z contrast of W atoms at a desired ratio.

[0115] In the reduction treatment step, the composite tungsten oxide particles obtained in the heat treatment step can be reduced by raising and lowering the temperature in a reducing atmosphere containing a reducing gas, that is, by performing heat treatment.

[0116] During the reduction treatment step, the composite tungsten oxide particles may be stirred or left to stand, and the handling of the composite tungsten oxide particles in the reduction treatment step can be appropriately selected, but it is preferable to select handling conditions such that metallic tungsten does not precipitate.

[0117] The temperature of the reduction treatment (reduction treatment temperature) is preferably higher than 400° C., more preferably 450° C. or higher, and further preferably 500° C. or higher.

[0118] The upper limit of the temperature of the reduction treatment is not particularly limited, but is preferably less than 700°C, more preferably 650°C or less, and further preferably less than 650°C.

[0119] In addition, when the raw material is a liquid, the particle size obtained in the aerosol formation process becomes smaller when the raw material concentration is reduced. Since the particles with a smaller diameter are easier to reduce, the temperature in the reduction process can be lowered than before. In the reduction process, the temperature can be raised from room temperature to the reduction temperature and then lowered back to room temperature.

[0120] The reduction conditions can be determined based on the optical properties of the resulting composite tungsten oxide particles.

[0121] By setting the reduction temperature to more than 400° C., the reduction process of the composite tungsten oxide particles can be advanced, and the infrared absorption properties can be more reliably exhibited. In addition, by setting the temperature to less than 700° C., the reduction of the composite tungsten oxide particles to metallic tungsten can be suppressed.

[0122] The reducing atmosphere is preferably an atmosphere of a mixed gas of an inert gas such as argon and a reducing gas such as H2 gas (hydrogen gas), and the reducing gas is preferably H2 gas.

[0123] When H2 gas is used as the reducing gas, the content of H2 gas in the reducing atmosphere can be appropriately selected, but the content of H2 gas is preferably in the range of 0.1% to 10% by volume, more preferably in the range of 2% to 10%. If reduction is performed in an atmosphere containing only reducing gas, the reduction reaction may proceed excessively and metallic tungsten may be precipitated, so care must be taken.

[0124] The time of the reduction process is preferably 30 minutes or more in total from temperature rise to temperature fall. The upper limit of the time of the reduction process is not particularly limited, and it is preferable to select it by performing a preliminary test or the like so that the reduction does not proceed excessively. The total time from temperature rise to temperature fall here means the time from starting temperature rise from room temperature to reaching the reduction treatment temperature and then cooling to room temperature. It is preferable that the composite tungsten oxide particles are placed in the reducing atmosphere described above during this time.

[0125] By carrying out the reduction treatment step in this manner, it is possible to convert undesired heterogeneous phases in the composite tungsten oxide particles obtained after the heat treatment step into the desired composite tungsten oxide phase. (1-5) Grinding process, classification process The method for producing composite tungsten oxide particles of the present embodiment may further include any steps, for example, a pulverization step or a classification step.

[0126] In the pulverization step, the composite tungsten oxide particles obtained in the reduction treatment step are pulverized, so that the particle size characteristics, such as the average particle size and the coefficient of variation, can be adjusted to fall within a desired range.

[0127] The conditions of the pulverization step are not particularly limited, and the composite tungsten oxide particles can be pulverized, etc., to obtain the desired particle size characteristics. For example, the composite tungsten oxide particles can be pulverized in a liquid medium using a medium stirring mill, etc., according to the method described later in the dispersing treatment method for a near-infrared absorbing particle dispersion in a liquid medium.

[0128] After the pulverization step, the liquid medium may be removed as necessary to recover the composite tungsten oxide particles. The method for removing the liquid medium is not particularly limited, but the liquid medium may be removed, for example, by carrying out a drying step or the like, which will be described later in the method for producing a near-infrared absorbing particle dispersion.

[0129] In addition, the method for producing the composite tungsten oxide particles of the present embodiment can also have a classification process for classifying the composite tungsten oxide particles in order to adjust the particle size distribution of the composite tungsten oxide particles. In the classification process, the specific method for classifying the composite tungsten oxide particles is not particularly limited, and can be selected according to the particle size of the composite tungsten oxide particles, etc. (2) Apparatus that can be suitably used in the method for producing composite tungsten oxide particles (2-1) Composite material manufacturing equipment An example of the configuration of a composite material production apparatus that can be suitably used in the method for producing composite tungsten oxide particles of this embodiment will be described below.

[0130] FIG. 1 is a schematic diagram of a composite material manufacturing apparatus 10 according to the present embodiment.

[0131] The composite material manufacturing apparatus 10 has a storage section 11 containing the raw material solution, a two-fluid nozzle 12 that forms droplets of the raw material and also forms a flame, and a reaction tube 13 connected to a filter 14 that collects the formed composite tungsten oxide particles. As already explained, the raw material solution can be a solution containing an M element source and a W element source.

[0132] Aerosol can be formed by supplying the raw material solution and carrier gas to the two-fluid nozzle 12 (aerosol formation process). For example, oxygen and a hydrocarbon can be supplied to the two-fluid nozzle 12, which together form a flame reaction field, and the formed aerosol can be supplied into the flame and subjected to heat treatment (heat treatment process). Cooling water piping 131 is arranged around the reaction tube 13, and the cooling water circulates. The composite tungsten oxide particles introduced into the reaction tube 13 are collected by a filter 14 such as a bag filter.

[0133] In addition, an ejector 15 may be provided on the most downstream side to adjust the supply amount of carrier gas.

[0134] Here, an example of the configuration of a composite material manufacturing apparatus is shown in which droplets of raw material are formed, heat-treated using a flame, and composite tungsten oxide particles are formed; however, the present invention is not limited to this form, and the raw material may be a powder or the like, and the heat source used for the heat treatment may be an electric furnace or the like. (2-2) Reduction treatment device In the reduction treatment device, the reduction treatment process described above can be carried out.

[0135] The reduction treatment device is not particularly limited as long as it is configured to perform the reduction treatment step described above. For example, the reduction treatment device may include a container for storing composite tungsten oxide particles obtained by the composite material production device described above, a gas pipe for supplying a mixed gas to the container to form a reducing atmosphere, and a heat source for heating the container.

[0136] It is also possible to introduce a mixed gas that forms a reducing atmosphere into the container, exhaust the gas, and place the composite tungsten oxide particles that are the object to be treated under a gas flow of the mixed gas. In this case, a supply pipe for the mixed gas and an exhaust pipe can be provided as gas pipes so that such a gas flow can be formed.

[0137] Furthermore, a stirring blade for stirring the composite tungsten oxide particles in the container may also be used in combination.

[0138] FIG. 2 is a diagram showing a schematic configuration example of a reduction treatment device, and shows a cross-sectional view taken along a plane passing through the central axis of a reaction tube 21 of a reduction treatment device 20. In FIG.

[0139] The reduction treatment device 20 is a horizontal tubular furnace, and can be used by attaching a gas inlet pipe (not shown) to one port 21A of the reaction tube 21 and a gas exhaust pipe (not shown) to the other port 21B of the tubular furnace. Then, by supplying a mixed gas that forms a reducing atmosphere from the one port 21A side, the inside of the reaction tube 21 can be made into a reducing atmosphere.

[0140] A heater 22 can be provided around the reaction tube 21, and the composite tungsten oxide particles can be placed in a ceramic container 23 such as a boat and placed at a position corresponding to the heater 22 in the reaction tube 21 of the tubular furnace.

[0141] By using the reduction treatment device 20, the inside of the reaction tube 21 is made into a reducing atmosphere and heated to a desired temperature by the heater 22, whereby the reduction treatment of the composite tungsten oxide particles 24 placed in the container 23 can be performed. [Near infrared absorbing particle dispersion] Next, a configuration example of the near infrared absorbing particle dispersion liquid of this embodiment will be described.

[0142] The near-infrared absorbing particle dispersion liquid of the present embodiment can contain near-infrared absorbing particles and a liquid medium. The near-infrared absorbing particles can be the above-mentioned composite tungsten oxide particles.

[0143] As the liquid medium, for example, one or more types selected from water, an organic solvent, oils and fats, liquid resins, and liquid plasticizers can be used. That is, for example, as shown in Fig. 3, a near-infrared absorbing particle dispersion 30 of the present embodiment can contain near-infrared absorbing particles 31 and a liquid medium 32. The near-infrared absorbing particle dispersion preferably has a configuration in which near-infrared absorbing particles are dispersed in a liquid medium.

[0144] 3 is a schematic diagram, and the near-infrared absorbing particle dispersion of this embodiment is not limited to this form. For example, in FIG. 3, the near-infrared absorbing particles 31 are represented by circles and described as spherical particles, but the shape of the near-infrared absorbing particles 31, which are the composite tungsten oxide particles described above, is not limited to this form and can have any shape. The near-infrared absorbing particles 31 can also have a coating on the surface, for example. The near-infrared absorbing particle dispersion 30 can contain other additives as necessary in addition to the near-infrared absorbing particles 31 and the liquid medium 32.

[0145] As described above, the liquid medium may be one or more selected from water, organic solvents, oils and fats, liquid resins, and liquid plasticizers.

[0146] As the organic solvent, various solvents such as alcohols, ketones, esters, hydrocarbons, glycols, etc. can be selected. Specifically, alcohol solvents such as isopropyl alcohol, methanol, ethanol, 1-propanol, isopropyl alcohol, butanol, pentanol, benzyl alcohol, diacetone alcohol, 1-methoxy-2-propanol, etc.; ketone solvents such as dimethyl ketone, acetone, methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, cyclohexanone, isophorone, etc.; ester solvents such as 3-methyl-methoxy-propionate, butyl acetate, etc.; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethyl Examples of the alkyl group include one or more selected from glycol derivatives such as propylene glycol isopropyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, and propylene glycol ethyl ether acetate; amides such as formamide, N-methylformamide, dimethylformamide, dimethylacetamide, and N-methyl-2-propylidone; aromatic hydrocarbons such as toluene and xylene; and halogenated hydrocarbons such as ethylene chloride and chlorobenzene.

[0147] However, among these, organic solvents with low polarity are preferred, and in particular, isopropyl alcohol, ethanol, 1-methoxy-2-propanol, dimethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether acetate, n-butyl acetate, etc. These organic solvents can be used alone or in combination of two or more kinds.

[0148] Examples of fats and oils that can be used include one or more selected from drying oils such as linseed oil, sunflower oil, and tung oil; semi-drying oils such as sesame oil, cottonseed oil, rapeseed oil, soybean oil, and rice bran oil; non-drying oils such as olive oil, coconut oil, palm oil, and dehydrated castor oil; fatty acid monoesters obtained by directly esterifying fatty acids of vegetable oils with monoalcohols; ethers; and petroleum-based solvents such as Isopar (registered trademark) E, Exxor (registered trademark) Hexane, Heptane, E, D30, D40, D60, D80, D95, D110, and D130 (all manufactured by ExxonMobil).

[0149] As the liquid resin, for example, one or more types selected from liquid acrylic resin, liquid epoxy resin, liquid polyester resin, liquid urethane resin, and the like can be used.

[0150] As the liquid plasticizer, for example, a liquid plasticizer for plastics can be used.

[0151] The components contained in the near infrared ray absorbing particle dispersion are not limited to the near infrared ray absorbing particles and the liquid medium described above. The near infrared ray absorbing particle dispersion may further contain any optional components added thereto as necessary.

[0152] For example, an acid or an alkali may be added to the near infrared absorbing particle dispersion liquid as necessary to adjust the pH of the dispersion liquid.

[0153] In addition, in order to further improve the dispersion stability of the near infrared absorbing particles in the near infrared absorbing particle dispersion liquid described above and to prevent the dispersed particle size from becoming coarse due to reaggregation, various surfactants, coupling agents, and the like can be added to the near infrared absorbing particle dispersion liquid as dispersants.

[0154] The dispersant such as the surfactant and coupling agent can be selected according to the application, but the dispersant preferably has one or more functional groups selected from an amine-containing group, a hydroxyl group, a carboxyl group, and an epoxy group. These functional groups adsorb to the surface of the near-infrared absorbing particles to prevent aggregation, and have the effect of dispersing the near-infrared absorbing particles uniformly even in the infrared shielding film formed using the near-infrared absorbing particles. A polymer dispersant having one or more functional groups selected from the above functional groups (functional groups) in the molecule is more preferable.

[0155] Suitable commercially available dispersants include Solsperse (registered trademark) 9000, 12000, 17000, 20000, 21000, 24000, 26000, 27000, 28000, 32000, 35100, 54000, and 250 (manufactured by Lubrizol Japan Co., Ltd.), and EFKA (registered trademark). 4008, 4009, 4010, 4015, 4046, 4047, 4060, 4080, 7462, 4020, 4050, 4055, 4400, 4401, 4402, 4403, 4300, 4320, 4330, 4340, 6220, 6225, 6700, 6780, 6782, 8503 (manufactured by F-Ka Additives), AJISPER (registered trademark) PA111, PB821, PB822, PN411, Famex L-12 (manufactured by Ajinomoto Fine-Techno Co., Ltd.), DisperBYK (registered trademark) 101, 102, 106, 108, 111, 116, 130, 140, 142, 145, 161, 162, 163, 164, 166, 167, 168, 170, 171, 174, 180, 182, 192, 193, 2000, 2001, 2020, 2025, 2050, 2070, 2155, 2164, 220S, 300, 306, 320, 322, 325, 330, 340, 350, 377, 378, 380N, 410, 425, 430 (manufactured by Pick Chemi-Japan Co., Ltd.), Disparon (registered trademark) Examples of the suitable polyimide resin include one or more selected from the group consisting of 1751N, 1831, 1850, 1860, 1934, DA-400N, DA-703-50, DA-725, DA-705, DA-7301, DN-900, NS-5210, and NVI-8514L (manufactured by Kusumoto Chemicals Co., Ltd.), Arfon (registered trademark) UC-3000, UF-5022, UG-4010, UG-4035, and UG-4070 (manufactured by Toagosei Co., Ltd.).

[0156] The method of dispersing the near infrared absorbing particles in the liquid medium is not particularly limited as long as it can disperse the near infrared absorbing particles in the liquid medium. In this case, it is preferable that the near infrared absorbing particles are dispersed so that the average particle size is 200 nm or less, more preferably 0.1 nm or more and 200 nm or less, and even more preferably 5 nm or more and 200 nm or less.

[0157] Examples of the dispersion method of near-infrared absorbing particles in a liquid medium include dispersion methods using devices such as a bead mill, a ball mill, a sand mill, a paint shaker, and an ultrasonic homogenizer. Among them, the dispersion method is preferably a method of pulverizing and dispersing using a medium agitation mill such as a bead mill, a ball mill, a sand mill, or a paint shaker using a medium media (beads, balls, Ottawa sand) from the viewpoint of shortening the time required to obtain a desired average particle size. By the pulverization-dispersion treatment using a medium agitation mill, the near-infrared absorbing particles are dispersed in a liquid medium, and at the same time, the near-infrared absorbing particles are also atomized due to collisions between the near-infrared absorbing particles and collisions of the medium media with the near-infrared absorbing particles, and the near-infrared absorbing particles can be further atomized and dispersed. That is, the near-infrared absorbing particles are subjected to the pulverization-dispersion treatment.

[0158] The near infrared absorbing particles contained in the near infrared absorbing particle dispersion of this embodiment can be manufactured by the manufacturing method of the composite tungsten oxide particles described above. Therefore, the manufacturing method of the near infrared absorbing particles contained in the near infrared absorbing particle dispersion is preferably a manufacturing method that can directly synthesize near infrared absorbing particles with a particle diameter of 1 μm or less. If near infrared absorbing particles with a particle diameter of 1 μm or less are directly synthesized, the diameter of the grinding medium (media) used in combination with a bead mill, ball mill, or paint shaker in the dispersion treatment method can be reduced in order to make the average particle diameter of the near infrared absorbing particles within a desired range.

[0159] For example, in the dispersion method, the preferred diameter (outer diameter) of the grinding medium used in the media stirring mill is 0.3 mm or less, more preferably 0.2 mm or less. By using a small grinding medium (media) with a diameter of 0.3 mm or less, the kinetic energy of the grinding medium can be reduced. Therefore, the impact on the near-infrared absorbing particles before the dispersion treatment due to the collision of the grinding medium during the dispersion treatment can be reduced, and the damage to the near-infrared absorbing particles can be reduced.

[0160] During the dispersion process, the composite tungsten oxide particles, which are near-infrared absorbing particles, are damaged by the collision of the grinding medium, resulting in element loss. However, as described above, if the kinetic energy of the grinding medium is small, the damage caused by the collision to the composite tungsten oxide particles can also be reduced. Therefore, by selecting the dispersion conditions, such as the size of the grinding medium, in the dispersion process, it is also possible to select the number ratio of dark areas in the Z contrast of the W atoms in the near-infrared absorbing particles, which are composite tungsten oxide particles, after the dispersion process. For example, when the diameter of the grinding medium is 0.3 mm or less, the number ratio of dark areas in the Z contrast of the W atoms in the near-infrared absorbing particles, which are composite tungsten oxide particles, can be made almost the same before and after the dispersion process.

[0161] As described above, the average particle diameter of the near-infrared absorbing particles is more preferably 0.1 nm or more and 200 nm or less, and even more preferably 5 nm or more and 200 nm or less. This is because, if the average particle diameter is small, scattering of light in the visible light region due to geometric scattering or Mie scattering is reduced. Furthermore, for example, the near-infrared absorbing particle dispersion obtained by using the near-infrared absorbing particle dispersion liquid of this embodiment, in which the near-infrared absorbing particles are dispersed in a resin or the like, becomes like cloudy glass, and it is possible to avoid the fact that clear transparency cannot be obtained. That is, when the average particle diameter is 200 nm or less, the light scattering becomes weaker in the geometric scattering or Mie scattering mode and becomes a Rayleigh scattering mode. In the Rayleigh scattering region, the scattered light is proportional to the sixth power of the dispersed particle diameter, so that the scattering is reduced and the transparency is improved as the dispersed particle diameter decreases. And, when the average particle diameter is 100 nm or less, the scattered light becomes very small, which is more preferable. That is, it is particularly preferable that the average particle diameter of the near-infrared absorbing particles is 5 nm or more and 100 nm or less.

[0162] The dispersion state of the near-infrared absorbing particles in the near-infrared absorbing particle dispersion obtained by using the near-infrared absorbing particle dispersion of the present embodiment, in which the near-infrared absorbing particles are dispersed in a solid medium such as a resin, does not result in aggregation greater than the average particle size of the near-infrared absorbing particles in the dispersion, as long as a known method for adding the dispersion to the solid medium is used.

[0163] In addition, when the average particle size of the near-infrared absorbing particles is 0.1 nm or more and 200 nm or less, it is possible to prevent the produced near-infrared absorbing particle dispersion and its molded body (plate, sheet, etc.) from becoming grayish in color with a monotonically decreasing transmittance.

[0164] The content of the near infrared absorbing particles in the near infrared absorbing particle dispersion of the present embodiment is not particularly limited, but is preferably, for example, 0.01% by mass or more and 80% by mass or less. This is because the content of the near infrared absorbing particles is 0.01% by mass or more, and therefore sufficient solar radiation transmittance can be exhibited, that is, the solar radiation transmittance can be sufficiently suppressed. In addition, the content of the near infrared absorbing particles is 80% by mass or less, and therefore the near infrared absorbing particles can be uniformly dispersed in the liquid medium, which is the dispersion medium.

[0165] According to the near-infrared absorbing particle dispersion liquid of the present embodiment, since it contains the above-described composite tungsten oxide particles, it is possible to provide a near-infrared absorbing particle dispersion liquid which has excellent visible light transmitting performance and infrared shielding performance, and also has excellent transmittance of light with a wavelength of 800 nm.

[0166] According to the near-infrared absorbing particle dispersion of this embodiment, even if the transmittance peak in the wavelength region of 450 nm or more and 600 nm or less is 80% or more, the transmittance bottom in the near-infrared region can be 10% or less, and thus the near-infrared absorbing particle dispersion has an excellent infrared shielding effect. That is, according to the near-infrared absorbing particle dispersion of this embodiment, a near-infrared absorbing particle dispersion excellent in visible light transmission performance and infrared shielding performance can be obtained. Furthermore, the near-infrared absorbing particle dispersion of this embodiment can increase the transmittance of red light in the vicinity of a wavelength of 800 nm compared to the dispersion of composite tungsten oxide particles shown in Comparative Example 1. Therefore, it can also contribute to improving the color tone of the near-infrared absorbing particle dispersion. For example, when the transmittance at a wavelength of 600 nm is 75% or more in the transmitted light profile, the near-infrared absorbing particle dispersion of this embodiment can achieve a transmittance of 50% or more at a wavelength of 700 nm, a transmittance of 20% or more at a wavelength of 800 nm, and a transmittance of 15% or less at a wavelength of 1000 nm. The transmittance at a wavelength of 800 nm can be more desirably 25% or more.

[0167] The near-infrared absorbing particle dispersion of the present embodiment transmits light of longer wavelengths in the visible light range more easily than the conventionally known composite tungsten oxide particle dispersion, resulting in a more neutral color tone. On the other hand, the near-infrared absorbing particle dispersion can achieve a transmittance of 15% or less at a wavelength of 1000 nm in the near-infrared range, so that it can block infrared rays in the same way as the conventionally known composite tungsten oxide particle dispersion.

[0168] That is, according to the near infrared absorbing particle dispersion liquid of this embodiment, while suppressing the solar radiation transmittance, the transmitted color has a more neutral color tone and the transmittance of the sensor wavelength can be ensured. [Near infrared absorbing particle dispersion] Next, a configuration example of the near infrared absorbing particle dispersion of the present embodiment will be described.

[0169] The near-infrared absorbing particle dispersion of this embodiment includes near-infrared absorbing particles and a solid medium. The near-infrared absorbing particles can be the composite tungsten oxide particles described above. Specifically, for example, as shown in FIG. 4, the near-infrared absorbing particle dispersion 40 can include near-infrared absorbing particles 41, which are the composite tungsten oxide particles described above, and a solid medium 42, and the near-infrared absorbing particles 41 can be disposed in the solid medium 42. In the near-infrared absorbing particle dispersion of this embodiment, the near-infrared absorbing particles are preferably dispersed in the solid medium. Note that FIG. 4 is a schematic diagram, and the near-infrared absorbing particle dispersion of this embodiment is not limited to this form. For example, in FIG. 4, the near-infrared absorbing particles 41 are represented by circles and described as spherical particles, but the shape of the near-infrared absorbing particles 41 is not limited to this form and can have any shape. The near-infrared absorbing particles 41 can also have a coating or the like on the surface. The near infrared absorbing particle dispersion 40 may contain, in addition to the near infrared absorbing particles 41 and the solid medium 42, other additives as necessary.

[0170] The near infrared absorbing particle dispersion according to this embodiment will be described below in the order of (1) properties of the solid medium and the near infrared absorbing particle dispersion, (2) a method for producing the near infrared absorbing particle dispersion, (3) additives, and (4) application examples. (1) Characteristics of solid media and near-infrared absorbing particle dispersions The solid medium may be a medium resin such as a thermoplastic resin, a thermosetting resin, an ultraviolet-curing resin, etc. That is, a resin may be suitably used as the solid medium.

[0171] The specific material of the resin used for the solid medium is not particularly limited, but is preferably one resin selected from the group consisting of polyester resin, polycarbonate resin, acrylic resin, styrene resin, polyamide resin, polyethylene resin, vinyl chloride resin, olefin resin, epoxy resin, polyimide resin, fluororesin, ethylene-vinyl acetate copolymer, polyvinyl acetal resin, and ultraviolet curing resin, or a mixture of two or more resins selected from the above group. As the polyester resin, polyethylene terephthalate resin can be preferably used.

[0172] These medium resins may also contain a polymeric dispersant having, in the main skeleton, one or more functional groups selected from an amine-containing group, a hydroxyl group, a carboxyl group, and an epoxy group.

[0173] The solid medium is not limited to a resin medium, and a binder using a metal alkoxide can also be used as the solid medium. Representative examples of the metal alkoxide include alkoxides of Si, Ti, Al, Zr, etc. By subjecting the binder using these metal alkoxides to hydrolysis and condensation polymerization by heating, etc., it is also possible to obtain a near-infrared absorbing particle dispersion in which the solid medium contains an oxide.

[0174] The content ratio of the near infrared absorbing particles in the near infrared absorbing particle dispersion according to this embodiment is not particularly limited, but the near infrared absorbing particle dispersion preferably contains the near infrared absorbing particles in an amount of 0.001 mass % or more and 80 mass % or less.

[0175] The shape of the near infrared absorbing particle dispersion of this embodiment is not particularly limited, but the near infrared absorbing particle dispersion of this embodiment preferably has a sheet shape, a board shape, or a film shape, because the near infrared absorbing particle dispersion in the sheet shape, board shape, or film shape can be applied to various applications.

[0176] According to the near infrared absorbing particle dispersion of the present embodiment, since it contains the above-described composite tungsten oxide particles, it is possible to provide a near infrared absorbing particle dispersion having excellent visible light transmittance and infrared shielding performance, and also excellent transmittance of light with a wavelength of 800 nm.

[0177] In addition, the near-infrared absorbing particle dispersion of this embodiment has an excellent infrared shielding effect, in which the transmittance bottom in the near-infrared region can be 10% or less even if the transmittance peak in the wavelength region of 450 nm or more and 600 nm or less is 80% or more. That is, the near-infrared absorbing particle dispersion of this embodiment can be a near-infrared absorbing particle dispersion excellent in visible light transmission performance and infrared shielding performance. Furthermore, the near-infrared absorbing particle dispersion of this embodiment can increase the transmittance of red light in the vicinity of a wavelength of 800 nm compared to the case where the composite tungsten oxide particles shown in Comparative Example 1 are used as the near-infrared absorbing particles. Therefore, it can also contribute to improving the color tone of the near-infrared absorbing particle dispersion. For example, when the transmittance at a wavelength of 600 nm is 75% or more in the transmitted light profile, the near-infrared absorbing particle dispersion of this embodiment can achieve a transmittance of 50% or more at a wavelength of 700 nm, a transmittance of 20% or more at a wavelength of 800 nm, and a transmittance of 15% or less at a wavelength of 1000 nm. The transmittance at a wavelength of 800 nm can be more desirably 25% or more.

[0178] The near-infrared absorbing particle dispersion of the present embodiment transmits light of longer wavelengths in the visible light range more easily than the conventional composite tungsten oxide particle dispersion, resulting in a more neutral color tone. On the other hand, the near-infrared absorbing particle dispersion can achieve a transmittance of 15% or less at a wavelength of 1000 nm in the near-infrared range, so that it can block infrared rays in the same way as the conventional composite tungsten oxide particle dispersion.

[0179] That is, according to the near infrared absorbing particle dispersion of this embodiment, while suppressing the solar radiation transmittance, the transmitted color has a more neutral color tone and the transmittance of the sensor wavelength can be ensured. (2) Method for producing near-infrared absorbing particle dispersion The method for producing the near infrared ray absorbing particle dispersion of the present embodiment will be described below. Note that, here, only a configuration example of the method for producing the near infrared ray absorbing particle dispersion is shown, and the method for producing the near infrared ray absorbing particle dispersion described above is not limited to the following configuration example.

[0180] The near infrared absorbing particle dispersion of the present embodiment can be produced, for example, by using a master batch. In this case, the production method of the near infrared absorbing particle dispersion of the present embodiment can also include, for example, the following master batch production step.

[0181] In the masterbatch preparation step, a masterbatch in which near-infrared absorbing particles are dispersed in a solid medium can be prepared.

[0182] A specific method for producing the master batch is not particularly limited. For example, the master batch can be produced by dispersing a near infrared absorbing particle dispersion liquid or near infrared absorbing particles in a solid medium and pelletizing the solid medium.

[0183] As the near-infrared absorbing particles, a near-infrared absorbing particle dispersion powder obtained by removing the liquid medium from a near-infrared absorbing particle dispersion liquid can also be used.

[0184] For example, a near-infrared absorbing particle dispersion, near-infrared absorbing particles, near-infrared absorbing particle dispersion powder, solid medium powder or pellets, and other additives as necessary are uniformly mixed to prepare a mixture. The mixture is then kneaded in a vented single-screw or twin-screw extruder, and processed into pellets by cutting melt-extruded strands, thereby producing a master batch. In this case, the shape of the pellets can be cylindrical or prismatic. In addition, when producing pellets, it is also possible to use the so-called hot-cut method in which the melt-extruded material is directly cut. In this case, the pellets generally have a shape close to a sphere.

[0185] In addition, when the near-infrared absorbing particle dispersion is used as a raw material in the master batch preparation process, it is preferable to reduce or remove the liquid medium derived from the near-infrared absorbing particle dispersion. In this case, the degree of removing the liquid medium contained in the near-infrared absorbing particle dispersion is not particularly limited. For example, it is preferable to remove the liquid medium from the near-infrared absorbing particle dispersion or the like to an amount that is allowed to remain in the master batch. In addition, when a liquid plasticizer is used as the liquid medium, the entire amount of the liquid plasticizer may remain in the near-infrared absorbing particle dispersion.

[0186] There is no particular limitation on the method for reducing or removing the liquid medium contained in the near-infrared absorbing particle dispersion from the near-infrared absorbing particle dispersion or the mixture of the near-infrared absorbing particle dispersion and the solid medium. For example, it is preferable to carry out a drying step for drying the near-infrared absorbing particle dispersion under reduced pressure. Specifically, the near-infrared absorbing particle dispersion is dried under reduced pressure while stirring, and the near-infrared absorbing particle-containing composition and the liquid medium components are separated. An example of the device used for the reduced pressure drying is a vacuum stirring type dryer, but any device having the above function may be used, and is not particularly limited. In addition, the pressure value during the reduced pressure in the drying step is appropriately selected.

[0187] By using the reduced pressure drying method, the efficiency of removing the liquid medium derived from the near-infrared absorbing particle dispersion liquid is improved. In addition, the near-infrared absorbing particle dispersion powder obtained after the reduced pressure drying and the near-infrared absorbing particle dispersion liquid as the raw material are not exposed to high temperatures for a long time, so that the near-infrared absorbing particle dispersion powder and the near-infrared absorbing particles dispersed in the near-infrared absorbing particle dispersion liquid do not aggregate, which is preferable. Furthermore, the productivity of the near-infrared absorbing particle dispersion powder etc. is increased, and it is easy to recover the solvent such as the evaporated liquid medium, which is also preferable from the environmental consideration.

[0188] In the near infrared absorbing particle dispersion powder etc. obtained after the drying step, it is preferable to thoroughly remove the solvent component having a boiling point of 120°C or less. For example, it is preferable that the residual amount of the solvent component is 2.5 mass% or less. If the residual solvent component is 2.5 mass% or less, when the near infrared absorbing particle dispersion powder etc. is processed into, for example, a near infrared absorbing particle dispersion, no air bubbles are generated, and the appearance and optical properties are maintained in a good condition. In addition, if the residual solvent component in the near infrared absorbing particle dispersion powder is 2.5 mass% or less, aggregation due to natural drying of the residual solvent component does not occur during long-term storage in the near infrared absorbing particle dispersion powder state, and long-term stability is maintained.

[0189] By adding a solid medium and kneading the obtained master batch, the dispersion concentration can be adjusted while maintaining the dispersed state of the near-infrared absorbing particles contained in the master batch, which is a near-infrared absorbing particle dispersion.

[0190] Furthermore, the manufacturing method for the near infrared absorbing particle dispersion of the present embodiment may include, as necessary, a molding step of molding the obtained master batch or the master batch to which a solid medium has been added as described above, to obtain a near infrared absorbing particle dispersion having a desired shape.

[0191] The specific method for molding the near infrared absorbing particle dispersion is not particularly limited, but for example, known methods such as extrusion molding and injection molding can be used.

[0192] In the molding step, for example, a near infrared absorbing particle dispersion can be produced in a sheet shape, a board shape, or a film shape formed into a flat or curved shape. The method for forming into a sheet shape, a board shape, or a film shape is not particularly limited, and various known methods can be used. For example, a calendar roll method, an extrusion method, a casting method, an inflation method, etc. can be used.

[0193] The method for producing the near infrared absorbing particle dispersion of the present embodiment is not limited to the embodiment having the above-mentioned master batch production step.

[0194] For example, the method for producing the near infrared absorbing particle dispersion of the present embodiment may have the following steps.

[0195] a precursor liquid preparation step of mixing a solid medium precursor, which is one or more types selected from a monomer, an oligomer, and an uncured liquid solid medium, with near-infrared absorbing particles, near-infrared absorbing particle dispersion powder, or near-infrared absorbing particle dispersion liquid to prepare a precursor liquid of a near-infrared absorbing particle dispersion.

[0196] A near-infrared absorbing particle dispersion preparation step in which the solid medium precursor such as the monomer is cured by a chemical reaction such as condensation or polymerization to prepare a near-infrared absorbing particle dispersion.

[0197] For example, when an acrylic resin is used as the solid medium, a near-infrared absorbing particle dispersion precursor liquid can be obtained by mixing an acrylic monomer or an acrylic ultraviolet curable resin with near-infrared absorbing particles.

[0198] Next, the near infrared ray absorbing particle dispersion precursor liquid is filled into a predetermined mold or the like and subjected to radical polymerization, thereby obtaining a near infrared ray absorbing particle dispersion using an acrylic resin.

[0199] When a resin that hardens by crosslinking is used as the solid medium, a dispersion can be obtained by subjecting a near infrared absorbing particle dispersion precursor liquid to a crosslinking reaction, similar to the case where the acrylic resin described above is used.

[0200] (3) Additives When a resin is used as the solid medium, the near infrared absorbing particle dispersion of the present embodiment may also contain known additives (additives) such as plasticizers, flame retardants, coloring inhibitors, and fillers that are usually added to these resins. However, as described above, the solid medium is not limited to resins, and a binder using a metal alkoxide may also be used.

[0201] The shape of the near infrared absorbing particle dispersion according to this embodiment is not particularly limited, but as described above, it can be in the form of, for example, a sheet, a board, or a film.

[0202] When the near infrared absorbing particle dispersion in sheet, board or film form is used as an intermediate layer of a transparent substrate such as laminated glass, the solid medium contained in the near infrared absorbing particle dispersion may not have sufficient flexibility or adhesion to the transparent substrate as it is.In this case, the near infrared absorbing particle dispersion preferably contains a plasticizer.Specifically, for example, when the solid medium is a polyvinyl acetal resin and used for the above-mentioned purpose, the near infrared absorbing particle dispersion preferably further contains a plasticizer.

[0203] As the above-mentioned plasticizer, a substance used as a plasticizer in the solid medium used in the near infrared absorbing particle dispersion of this embodiment can be used. For example, as a plasticizer used in the near infrared absorbing particle dispersion in which the solid medium is composed of a polyvinyl acetal resin, there can be mentioned a plasticizer that is a compound of a monohydric alcohol and an organic acid ester, an ester-based plasticizer such as a polyhydric alcohol organic acid ester compound, and a phosphoric acid-based plasticizer such as an organic phosphoric acid-based plasticizer. It is preferable that any plasticizer is liquid at room temperature. Among them, a plasticizer that is an ester compound synthesized from a polyhydric alcohol and a fatty acid is preferable. (4) Application Examples The near infrared absorbing particle dispersion of the present embodiment can be used in various aspects, and its use and application aspects are not particularly limited. Hereinafter, as application examples of the near infrared absorbing particle dispersion of the present embodiment, a near infrared absorbing intermediate film, a near infrared absorbing laminate, and a near infrared absorbing transparent substrate will be described. (4-1) Near-infrared absorbing interlayer film, near-infrared absorbing laminate The near infrared absorbing laminate of the present embodiment can have a laminate structure including the near infrared absorbing particle dispersion and a transparent substrate described above. The near infrared absorbing laminate of the present embodiment can be a laminate having the near infrared absorbing particle dispersion and a transparent substrate described above as elements, and can be a laminate obtained by laminating these elements.

[0204] The near-infrared absorbing laminate may be, for example, a laminate of two or more transparent substrates and the near-infrared absorbing particle dispersion described above. In this case, the near-infrared absorbing particle dispersion may be disposed between the transparent substrates and used as a near-infrared absorbing intermediate film.

[0205] In this case, specifically, as shown in Fig. 5 which is a cross-sectional schematic diagram along the lamination direction of the transparent substrate and the near-infrared absorbing particle dispersion, the near-infrared absorbing laminate 50 can have a plurality of transparent substrates 521, 522 and a near-infrared absorbing particle dispersion 51. The near-infrared absorbing particle dispersion 51 can be disposed between the plurality of transparent substrates 521, 522. Although Fig. 5 shows an example in which two transparent substrates 521, 522 are provided, the present invention is not limited to this embodiment.

[0206] The near infrared absorbing particle dispersion that becomes the near infrared absorbing intermediate film preferably has any one of a sheet shape, a board shape, and a film shape.

[0207] The transparent substrate may be one or more selected from the group consisting of plate glass, plate-like plastic, and film-like plastic, all of which are transparent in the visible light region.

[0208] When plastic is used as the transparent substrate, the material of the plastic is not particularly limited and can be selected according to the application, and can be, for example, one or more types selected from polycarbonate resin, acrylic resin, polyester resin, polyamide resin, vinyl chloride resin, olefin resin, epoxy resin, polyimide resin, ionomer resin, fluororesin, etc. As the polyester resin, polyethylene terephthalate resin can be preferably used.

[0209] The transparent substrate may contain particles having a solar radiation shielding function. As the particles having a solar radiation shielding function, near-infrared absorbing particles having a near-infrared shielding property can be used.

[0210] By interposing the near-infrared absorbing particle dispersion described above as a constituent member of the intermediate layer sandwiched between a plurality of transparent substrates, a solar radiation shading laminated structure, which is a type of near-infrared absorbing laminate having excellent visible light transmission performance and infrared shielding performance and excellent transmittance of light with a wavelength of 800 nm, can be obtained. In addition, the solar radiation shading laminated structure of this embodiment has an excellent infrared shielding effect, in which the peak of the transmittance in the wavelength region of 450 nm to 600 nm can be 80% or more, and the bottom of the transmittance in the near-infrared region can be 10% or less. That is, according to the solar radiation shading laminated structure of this embodiment, a solar radiation shading laminated structure having excellent visible light transmission performance and infrared shielding performance can be obtained. Furthermore, the solar radiation shading laminated structure of this embodiment can increase the transmittance of red light with a wavelength of around 800 nm compared to the case where the composite tungsten oxide particles shown in Comparative Example 1 are used as the near-infrared absorbing particles. Therefore, it can also contribute to improving the color tone of the solar radiation shading laminated structure. For example, when the transmittance at a wavelength of 600 nm is 75% or more in the transmitted light profile, the solar radiation shading combined structure of this embodiment can achieve a transmittance of 50% or more at a wavelength of 700 nm, a transmittance of 20% or more at a wavelength of 800 nm, and a transmittance of 15% or less at a wavelength of 1000 nm. The transmittance at a wavelength of 800 nm can be more preferably 25% or more.

[0211] For this reason, it is possible to obtain a solar radiation shading laminated structure that is a type of near-infrared absorbing laminate that has a more neutral transmitted color tone while suppressing the solar radiation transmittance and also ensures transmittance at the sensor wavelength.

[0212] The near-infrared absorbing laminate can also be obtained by bonding and integrating a plurality of transparent substrates facing each other with the near-infrared absorbing particle dispersion therebetween by a known method.

[0213] When the above-described near-infrared absorbing particle dispersion is used as a near-infrared absorbing interlayer film, the solid medium may be the same as that described for the near-infrared absorbing particle dispersion. However, from the viewpoint of increasing the adhesive strength between the near-infrared absorbing interlayer film and the transparent substrate, the solid medium is preferably a polyvinyl acetal resin.

[0214] The near-infrared absorbing interlayer film of the present embodiment can be produced by the above-described method for producing a near-infrared absorbing particle dispersion, and can be in the form of, for example, a sheet, a board, or a film.

[0215] In addition, when the near-infrared absorbing intermediate film does not have sufficient flexibility or adhesion to the transparent substrate, it is preferable to add a liquid plasticizer for the medium resin. For example, when the medium resin used in the near-infrared absorbing intermediate film is a polyvinyl acetal resin, the addition of a liquid plasticizer for the polyvinyl acetal resin is beneficial for improving adhesion to the transparent substrate.

[0216] As the plasticizer, a substance that is used as a plasticizer for a resin of a solid medium can be used. For example, examples of plasticizers that can be applied to a near infrared absorbing particle dispersion using a polyvinyl acetal resin as a solid medium include a plasticizer that is a compound of a monohydric alcohol and an organic acid ester, an ester-based plasticizer such as a polyhydric alcohol organic acid ester compound, and a phosphoric acid-based plasticizer such as an organic phosphoric acid-based plasticizer. It is preferable that any of the plasticizers is liquid at room temperature. Among them, a plasticizer that is an ester compound synthesized from a polyhydric alcohol and a fatty acid is preferable.

[0217] In addition, at least one selected from the group consisting of a silane coupling agent, a metal salt of a carboxylic acid, a metal hydroxide, and a metal carbonate can also be added to the near-infrared absorbing interlayer film. The metal constituting the metal salt of a carboxylic acid, the metal hydroxide, and the metal carbonate is not particularly limited, but is preferably at least one selected from sodium, potassium, magnesium, calcium, manganese, cesium, lithium, rubidium, and zinc. In the near-infrared absorbing interlayer film, the content of at least one selected from the group consisting of a metal salt of a carboxylic acid, a metal hydroxide, and a metal carbonate is preferably 1% by mass or more and 100% by mass or less relative to the near-infrared absorbing particles.

[0218] Furthermore, the near-infrared absorbing interlayer film may contain, in addition to the near-infrared absorbing particles as necessary, at least one of oxide particles, composite oxide particles, and boride particles containing two or more elements selected from the group consisting of Sb, V, Nb, Ta, W, Zr, F, Zn, Al, Ti, Pb, Ga, Re, Ru, P, Ge, In, Sn, La, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Tb, Lu, Sr, and Ca. The near-infrared absorbing interlayer film may contain such particles in an amount of 5% by mass or more and 95% by mass or less, assuming that the total amount of the particles and the near-infrared absorbing particles is 100% by mass.

[0219] In the near-infrared absorbing laminate, at least one layer of the intermediate film disposed between the transparent substrates may contain an ultraviolet absorbing agent. The ultraviolet absorbing agent may be one or more selected from a compound having a malonic acid ester structure, a compound having an oxalic acid anilide structure, a compound having a benzotriazole structure, a compound having a benzophenone structure, a compound having a triazine structure, a compound having a benzoate structure, a compound having a hindered amine structure, and the like.

[0220] Incidentally, it goes without saying that the intermediate layer of the near-infrared absorbing laminate may be composed only of the near-infrared absorbing intermediate film according to this embodiment.

[0221] The near-infrared absorbing intermediate film described here is one aspect of the near-infrared absorbing particle dispersion. The near-infrared absorbing particle dispersion according to this embodiment can be used without being sandwiched between two or more transparent substrates that transmit visible light. In other words, the near-infrared absorbing particle dispersion according to this embodiment can function alone as a near-infrared absorbing particle dispersion.

[0222] The near-infrared absorbing laminate according to the present embodiment is not limited to the above-described form in which a near-infrared absorbing particle dispersion is disposed between transparent substrates, and any configuration may be adopted as long as the near-infrared absorbing laminate has a layered structure including a near-infrared absorbing particle dispersion and a transparent substrate. (4-2) Near infrared absorbing transparent substrate The near-infrared absorbing transparent substrate of the present embodiment includes a transparent substrate and a near-infrared absorbing layer disposed on at least one surface of the transparent substrate, and the near-infrared absorbing layer can be the near-infrared absorbing particle dispersion described above.

[0223] 6, which is a cross-sectional schematic diagram along the lamination direction of the transparent substrate and the near-infrared absorbing layer, the near-infrared absorbing transparent substrate 60 can have a transparent substrate 61 and a near-infrared absorbing layer 62. The near-infrared absorbing layer 62 can be disposed on at least one surface 61A of the transparent substrate 61.

[0224] The near infrared absorbing transparent substrate of the present embodiment may have a transparent substrate as described above. As the transparent substrate, for example, one or more types selected from a transparent film substrate and a transparent glass substrate may be preferably used.

[0225] The film substrate is not limited to a film shape, and may be, for example, a board shape or a sheet shape. As the material of the film substrate, one or more selected from polyester resin, acrylic resin, urethane resin, polycarbonate resin, polyethylene resin, ethylene vinyl acetate copolymer, vinyl chloride resin, fluororesin, etc. can be suitably used, and can be used according to various purposes. However, as the material of the film substrate, polyester resin is preferable, and in particular polyethylene terephthalate resin (PET resin) is more preferable. That is, the film substrate is preferably a polyester resin film, and more preferably a polyethylene terephthalate resin film.

[0226] When a film substrate is used as the transparent substrate, the surface of the film substrate is preferably subjected to a surface treatment in order to facilitate adhesion to the near-infrared absorbing layer.

[0227] In order to improve the adhesion between the glass substrate or film substrate and the near-infrared absorbing layer, it is also preferable to form an intermediate layer on the glass substrate or film substrate and then form the near-infrared absorbing layer on the intermediate layer. The intermediate layer is not particularly limited in structure, and may be formed, for example, of a polymer film, a metal layer, an inorganic layer (e.g., an inorganic oxide layer such as silica, titania, or zirconia), an organic / inorganic composite layer, or the like.

[0228] The near infrared ray absorbing particle dispersion has been described above, and therefore the description thereof will be omitted here. The shape of the near infrared ray absorbing particle dispersion is not particularly limited, but it is preferable that the near infrared ray absorbing particle dispersion has a sheet shape, a board shape, or a film shape, for example.

[0229] A method for producing the near infrared absorbing transparent substrate of this embodiment will be described.

[0230] The near-infrared absorbing transparent substrate of the present embodiment can be produced, for example, by forming a near-infrared absorbing layer, which is a near-infrared absorbing particle dispersion in which near-infrared absorbing particles are dispersed in a solid medium, on a transparent substrate using the above-described near-infrared absorbing particle dispersion liquid.

[0231] Therefore, the method for producing the near-infrared absorbing transparent substrate of the present embodiment can include, for example, the following coating step and near-infrared absorbing layer forming step.

[0232] In the coating step, a coating liquid containing the above-described near-infrared absorbing particle dispersion is coated on the surface of a transparent substrate.

[0233] In the near-infrared absorbing layer forming step, the liquid medium in the coating liquid is evaporated, and then the near-infrared absorbing layer is formed.

[0234] The coating liquid used in the coating step can be prepared, for example, by adding and mixing a resin, a solid medium such as a metal alkoxide, or a solid medium precursor to the near infrared absorbing particle dispersion liquid described above.

[0235] As described above, the solid medium precursor refers to one or more selected from a monomer, an oligomer, and an uncured liquid solid medium of a solid medium.

[0236] When a near-infrared absorbing layer, which is a coating film, is formed on a transparent substrate, the near-infrared absorbing layer is in a state in which near-infrared absorbing particles are dispersed in a solid medium. Therefore, the near-infrared absorbing layer becomes a near-infrared absorbing particle dispersion. In this way, a near-infrared absorbing transparent substrate can be produced by providing a near-infrared absorbing particle dispersion on the surface of the transparent substrate.

[0237] The solid medium and the solid medium precursor have been described in (1) Characteristics of the solid medium and the near infrared absorbing particle dispersion and (2) Production method of the near infrared absorbing particle dispersion, and therefore description thereof will be omitted here.

[0238] In order to provide a near-infrared absorbing layer on a transparent substrate, the method of applying a coating liquid on the transparent substrate is not particularly limited as long as the coating liquid can be uniformly applied to the surface of the transparent substrate. For example, bar coating, gravure coating, spray coating, dip coating, spin coating, screen printing, roll coating, flow coating, etc. can be mentioned.

[0239] Here, the procedure for producing a near-infrared absorbing layer on the surface of a transparent substrate will be described using as an example a case in which an ultraviolet curable resin is used as a solid medium, a coating liquid is applied by a bar coating method, and a near-infrared absorbing layer is formed.

[0240] The coating solution, the concentration of which and the amount of additives are appropriately adjusted so as to have a suitable leveling property, is applied onto the transparent substrate using a wire bar with a bar number that can satisfy the thickness of the near-infrared absorbing layer and the content of the near-infrared absorbing particles as intended. Then, the solvent such as the liquid medium contained in the coating solution is removed by drying, and then the solid medium is cured by irradiating ultraviolet light, thereby forming a coating layer that is a near-infrared absorbing layer on the transparent substrate.

[0241] Drying conditions for the coating film vary depending on the type and proportion of each component and solvent, but can usually be performed under conditions of about 20 seconds to 10 minutes at a temperature of 60° C. to 140° C. There are no particular limitations on the ultraviolet irradiation, and an ultraviolet exposure device such as an ultra-high pressure mercury lamp can be suitably used.

[0242] In addition, the adhesion between the transparent substrate and the near-infrared absorbing layer, the smoothness of the coating film during coating, the drying property of the organic solvent, etc. can be manipulated by the pre- and post-processes (pre- and post-processes) before and after the formation of the near-infrared absorbing layer. Examples of the pre- and post-processes include a surface treatment process for the transparent substrate, a pre-baking process (pre-heating of the substrate), and a post-baking process (post-heating of the substrate), and can be appropriately selected. The heating temperature in the pre-baking process and the post-baking process is preferably 80° C. or higher and 200° C. or lower, and the heating time is preferably 30 seconds or higher and 240 seconds or lower.

[0243] The method for producing the near-infrared absorbing transparent substrate of the present embodiment is not limited to the above-mentioned method. Other configuration examples of the method for producing the near-infrared absorbing transparent substrate of the present embodiment include the following near-infrared absorbing particle dispersion coating and drying steps, and binder coating and curing steps.

[0244] In the near-infrared absorbing particle dispersion coating and drying process, the above-mentioned near-infrared absorbing particle dispersion is coated on the surface of the transparent substrate, and then dried.

[0245] In the binder coating and curing step, a binder using a solid medium such as a resin or a metal alkoxide, or a solid medium precursor is coated on the surface on which the near infrared absorbing particle dispersion liquid has been coated, and then cured.

[0246] In this case, a film having near-infrared absorbing particles dispersed therein is formed on the surface of the transparent substrate by the near-infrared absorbing particle dispersion coating and drying steps. The near-infrared absorbing particle dispersion can be coated by the same method as that described in the coating step of the above-mentioned method for producing a near-infrared absorbing transparent substrate.

[0247] Then, a binder is applied onto the film in which the near-infrared absorbing particles are dispersed, and then cured, so that the cured binder is disposed between the near-infrared absorbing particles, thereby forming a near-infrared absorbing layer.

[0248] The near infrared ray absorbing transparent substrate may further have a coating layer on the surface of the near infrared ray absorbing particle dispersion, that is, may have a multilayer film.

[0249] The coating layer can be, for example, a coating film of an oxide containing one or more selected from Si, Ti, Zr, and Al. In this case, the coating layer can be formed, for example, by applying a coating liquid containing one or more selected from alkoxides containing one or more of Si, Ti, Zr, and Al, and partial hydrolysis and condensation polymerization products of the alkoxides, onto the near-infrared absorbing layer, and then heating the coating liquid.

[0250] By providing a coating layer, the coated component fills the gaps between the accumulated near-infrared absorbing particles of the first layer to form a film, suppressing the refraction of visible light, thereby further reducing the haze value of the film and improving the visible light transmittance. In addition, the adhesion of the near-infrared absorbing particles to the substrate can be improved.

[0251] Here, as a method for forming a coating film made of an alkoxide containing one or more of Si, Ti, Zr, and Al, or a partial hydrolysis and condensation polymerization product thereof, on the near infrared absorbing particle alone or on a film containing the near infrared absorbing particle, a coating method is preferred from the viewpoints of ease of film formation operation and cost.

[0252] The coating liquid used in the above coating method can be preferably one containing at least one of alkoxides of Si, Ti, Zr, and Al in a solvent such as water or alcohol, or at least one of partial hydrolysis polycondensates of the alkoxides. The content of the alkoxides in the above coating liquid is not particularly limited, but is preferably 40 mass% or less in terms of oxide in the coating obtained after heating. In addition, the pH can be adjusted by adding an acid or alkali as necessary.

[0253] The coating liquid is applied as a second layer on a film mainly composed of near-infrared absorbing particles, and then heated to easily form an oxide film containing one or more selected from Si, Ti, Zr, and Al, which is a coating layer. It is also preferable to use an organosilazane solution as a binder component used in the coating liquid or as a component of the coating liquid.

[0254] The heating temperature of the substrate after application of the near infrared ray absorbing particle dispersion liquid containing one or more metal alkoxides of Si, Ti, Zr, and Al and their hydrolysis polymers, or the coating liquid, is not particularly limited. For example, the heating temperature of the substrate is preferably 100° C. or higher, and more preferably the heating temperature is higher than the boiling point of the solvent in the coating liquid such as the near infrared ray absorbing particle dispersion liquid.

[0255] This is because the polymerization reaction of the metal alkoxide or the hydrolysis polymer of the metal alkoxide contained in the coating film can be completed when the substrate heating temperature is 100° C. or higher. In addition, when the substrate heating temperature is 100° C. or higher, the solvent water or organic solvent hardly remains in the film, so that these solvents do not cause a decrease in the visible light transmittance of the film after heating.

[0256] The thickness of the near-infrared absorbing layer on the transparent substrate of the near-infrared absorbing transparent substrate of this embodiment is not particularly limited, but is preferably 10 μm or less in practical use, more preferably 6 μm or less. This is because, if the thickness of the near-infrared absorbing layer is 10 μm or less, it not only exhibits sufficient pencil hardness and has scratch resistance, but also prevents process abnormalities such as warping of the substrate film during the evaporation of the solvent and the hardening of the binder in the near-infrared absorbing layer. EXAMPLES

[0257] The present invention will be described below with reference to specific examples, but is not limited to these examples. (1) Evaluation method (1-1) Powder X-ray diffraction pattern The powder X-ray diffraction pattern (XRD pattern) of the composite tungsten oxide particles was measured using a powder X-ray diffractometer (BRUKER D2 PHASER). The powder X-ray diffraction pattern was measured using CuKα radiation as the radiation source, with a tube voltage of 45 kV and a tube current of 40 mA. (1-2) STEM and HAADF image observation The obtained composite tungsten oxide particles were observed using a transmission electron microscope. High-angle angular dark-field images (HAADF) were also observed using a JEOL STEM (model: JEM-ARM200F). The atomic number (Z) contrast in the HAADF image is proportional to the square of the atomic number of the atoms in the particle and the number of atoms. The more heavier atoms are stacked, the brighter the contrast, so the brightest and second brightest contrasts are W, and the third brightest contrast is Cs, and it is thought that O cannot be confirmed.

[0258] The sample was placed on a Cu mesh with a supporting film using the dispersion method and observed.

[0259] During the observation, a high angle scattering dark field image (STEM-HAADF) was obtained at an accelerating voltage of 200 kV. This observation image was obtained by detecting only the transmitted electrons with a large scattering angle among the electrons that had passed through the sample, and as described above, contrast due to differences in composition can be obtained. Note that since the magnitude of the scattering angle is proportional to the square of the atomic number (Z), the higher the atomic number of the element, the brighter the contrast. In the case of the composite tungsten oxide particles prepared in the examples and comparative examples, it is possible to distinguish Cs and W by the difference in contrast.

[0260] In the evaluation, we decided to use the difference in contrast intensity at tungsten columns (W columns), which are spots (points) where tungsten is placed, in the STEM-HAADF image to distinguish between areas with and without defects in W. If there is a defect in W, the maximum value of Z contrast at that spot decreases.

[0261] The contrast of the observed STEM-HAADF images was evaluated and observed using Digital Micrograph (Version 3.43.3213.0) manufactured by Gatan. The observed data was read into this software, and the contrast of the relevant area was extracted using the line profile function.

[0262] For the STEM-HAADF images, particles with a size of 50 nm or more were selected from the dispersed composite tungsten oxide particles to suppress degradation by the electron beam. The particle size used to select the particles to be observed was the diameter of the smallest inclusive circle that contained the particle. In addition, the size of the observation field was set to 20 nm square or more and 50 nm square or less to clearly distinguish the Z contrast of W atoms.

[0263] Figure 7 shows the hexagonal Cs-WO compound. 0.33 The figure shows the crystal structure of WO3 in the

[0001] incidence direction, i.e., on the (001) plane. There are W / W rows 701 in which only W atoms 71 are lined up, and W / Cs rows 702 in which W atoms 71 and Cs atoms, which are M elements 73, are alternately arranged. Note that the region S between the double arrows indicating the a-axis length and b-axis length in the figure forms a unit lattice. W columns and Cs columns exist in the c-axis direction, which is perpendicular to the paper surface, and there are three rows of W columns and one row of Cs columns per region S. When calculating the percentage of dark areas in the Z contrast of tungsten atoms in the STEM-HAADF image, we first counted the number of W columns in the observation field of view with reference to the crystal structure shown in Figure 7.

[0264] Next, the maximum value of the Z contrast of each W column spot in the observation field was calculated using the above software, and the average value was calculated. In addition, the number of dark areas, which are spots where the maximum value of the contrast of each W column spot in the observation field was 95% or less of the average value, was counted.

[0265] Then, the ratio of the number of dark areas in the observation field to the number of W columns in the observation field was calculated. (1-3) Transmitted light profile The optical characteristics of the near-infrared absorbing particle dispersion were measured by measuring the transmitted light profile at 5 nm intervals in the wavelength range of 200 nm to 2600 nm using a spectrophotometer (U-4100 manufactured by Hitachi, Ltd.). (1-4) Composition analysis The proportion of each component contained in the composite tungsten oxide particles was evaluated by the following method.

[0266] The mass fraction of Cs was calculated as the average value of three measurements for each sample using a polarized Zeeman atomic absorption spectroscopy (AAS, model: ZA3300, Hitachi High-tec Corporation).

[0267] The mass fraction of W was determined as the average value of three analyses for each sample using inductively-coupled plasma optical emission spectroscopy (ICP-OES, model: ICPE-9800, manufactured by Shimadzu Corporation).

[0268] The mass percentage of O was calculated as the average value of three analyses for each sample using an infrared detector for oxygen detection (infrared absorption spectroscopy (IRS)) on an oxygen / nitrogen / hydrogen analyzer (ON-836, LECO Japan Corp.). [Example 1] Composite tungsten oxide particles were produced and evaluated using the composite material production apparatus 10 shown in Fig. 1 and the reduction treatment apparatus 20 shown in Fig. 2. Specific conditions will be described below.

[0269] The composite material manufacturing apparatus 10 has a storage section 11 containing a solution containing a W element source and an M element source, which are raw material solutions, a two-fluid nozzle 12 that forms droplets of the raw materials and also forms a flame, and a reaction tube 13 connected to a filter 14 that collects the formed composite tungsten oxide particles.

[0270] The supply rate of the raw material solution to the two-fluid nozzle 12 was set to 3 g / min. The flow rate of oxygen, which was a carrier gas, was set to 15 L / min, controlled by the ejector 15. The air flow rate in the ejector 15 was controlled to be within the range of 160 L / min to 180 L / min.

[0271] Propane gas and oxygen gas were used to form a flame by the two-fluid nozzle 12, with the propane gas flow rate set to 1.2 L / min and the oxygen gas flow rate set to 6.0 L / min.

[0272] As the raw material, a mixed solution of a solution in which W(CO)6, the W element source, is dissolved in THF (tetrahydrofuron) (a solution containing a W element source) and a solution in which cesium acetate, the M element source, is dissolved in ethanol (a solution containing an M element source) was used and stored in the storage unit 11. The mixed solution, the raw material, was prepared so that the ratio of the amount of substance of Cs (Cs) contained in the M element to the amount of substance of tungsten (W) was Cs / W, which was 0.37.

[0273] The raw material solution and oxygen as a carrier gas were supplied from the storage section 11 to the two-fluid nozzle 12 to form an aerosol (aerosol forming step).

[0274] As described above, propane gas and oxygen gas were supplied to the two-fluid nozzle 12 to form a flame reaction field, and the formed aerosol was supplied into the flame to perform heat treatment (heat treatment step).

[0275] In the heat treatment process, the heat treatment conditions were selected so that the composite tungsten oxide particles obtained after the heat treatment process would have appropriate W atom deficiencies and heterogeneous phases, and would have composite tungsten oxide particles in which spots with reduced W atom Z contrast were confirmed after the reduction treatment process. Specifically, the heat treatment conditions were selected based on the results of tests carried out in advance. In the heat treatment process, the raw material was heat-treated at a temperature of 550°C or higher.

[0276] The composite tungsten oxide particles obtained in the heat treatment step were introduced into reaction tube 13. Cooling water piping 131 was arranged around reaction tube 13, and cooling water was circulating. The composite tungsten oxide particles introduced into reaction tube 13 were collected by filter 14, which was a bag filter. When the composite tungsten oxide particles collected by the bag filter were observed by STEM, the particle size was found to be 1 μm or less.

[0277] The composite tungsten oxide particles obtained after the heat treatment step were evaluated for their XRD patterns.

[0278] FIG. 8 shows the XRD pattern of the obtained composite tungsten oxide particles. In FIG. 8, the XRD pattern (A) shown as "As produced" is the XRD pattern of the composite tungsten oxide particles after the heat treatment process. Hexagonal Cs 0.33 WO3 (ICDD:81-1245) or orthorhombic Cs4W 11 O 35 (ICDD: 51-1891) and a small amount of cubic pyrochlore (CsO). 0.44 The phase was identified as W2O6 (ICDD:47-0566). The minor crystalline phase was identified using Rietveld analysis.

[0279] Further, reduction treatment was carried out using the reduction treatment device 20 shown in FIG.

[0280] 2, under an airflow of 3 vol% H2 / 97 vol% Ar, a heater 22 was provided around a reaction tube 21, the temperature was raised from room temperature to 500°C, and after the part where the container 23 was placed reached the reduction treatment temperature, it was held for 2 hours, and then cooled to room temperature to perform reduction treatment (reduction treatment step). As a result, reduced particles (reduced particles A), which are composite tungsten oxide particles according to Example 1, were obtained.

[0281] FIG. 8 shows the XRD pattern of the obtained composite tungsten oxide particles. In FIG. 8, the XRD pattern (B) shown as "Heat treated" is the XRD pattern of the composite tungsten oxide particles after the reduction treatment step. The obtained XRD pattern shows that Cs 0.33 It was confirmed that the crystal system was hexagonal, containing only the diffraction peaks of WO3.

[0282] The composite tungsten oxide particles, which are the reduced particles A after the reduction process according to Example 1, were subjected to the composition analysis described above, and the Cs / W ratio, which is the ratio of the amount of substance between cesium and tungsten, was obtained. As a result, it was confirmed that the Cs / W ratio decreased from 0.37 in the charged composition to 0.34. However, the value of 0.34 is 0.01 more than the theoretical composition ratio of 0.33, and since the above XRD pattern shows a single phase, it is considered that there is almost no Cs deficiency.

[0283] In addition, a composition analysis of the composite tungsten oxide particles confirmed that the O / W ratio, which is the ratio of the amount of oxygen to tungsten, was 2.841. In the following explanation, the composite tungsten oxide particles will be evaluated using XRD patterns and Cs 0.33 It is written as WO3.

[0284] The materials were weighed out so that the proportions were 1 mass% of reduced particles A, 5 mass% of an acrylic polymer dispersant (amine value 48 mgKOH / g) having an amine-containing functional group (hereinafter referred to as "dispersant a"), and 94 mass% of methyl isobutyl ketone. The weighed out materials were placed in a paint shaker together with zirconia beads having a diameter of 0.05 mm, and a dispersion treatment was carried out for 120 minutes using the paint shaker to obtain a near-infrared absorbing particle dispersion liquid according to Example 1.

[0285] The number-based average particle size (measured by a transmission electron microscope) of the composite tungsten oxide particles in the dispersion liquid according to Example 1 obtained was 16.96 nm. The particle size characteristics such as the number-based average particle size of the composite tungsten oxide particles in the dispersion liquid according to Example 1 are shown in Table 1. The coefficient of variation is the standard deviation of the number-based particle size distribution divided by the number-based average particle size. The number-based median diameter of the composite tungsten oxide particles is also shown.

[0286] The average particle size of the composite tungsten oxide particles was calculated by observing three fields of view using a transmission electron microscope. Specifically, images of a total of 600 to 700 composite tungsten oxide particles were observed in three fields of view, and the area of ​​each particle was calculated from the binarized data, and the circular equivalent diameter of each particle was calculated. The three fields of view were set to a magnification that included 200 or more composite tungsten oxide particles in one field of view. The particle sizes of all the composite tungsten oxide particles evaluated, that is, the arithmetic mean value of the circular equivalent diameters, was taken as the average particle size.

[0287] The near infrared absorbing particle dispersion liquid according to Example 1 was separated, and the solvent was removed to obtain composite tungsten oxide particles according to Example 1.

[0288] STEM-HAADF images of the composite tungsten oxide particles according to Example 1 are shown in Fig. 9(A) and Fig. 9(B). Fig. 9(A) shows a STEM-HAADF image of the entire particle. Fig. 9(B) shows an image obtained by enlarging and observing a square region 91 in the particle shown in Fig. 9(A). As shown in Fig. 9(B), the size of the observation field was adjusted to be about 20 nm square. About 15 dark areas, which are regions with low Z contrast of W atoms, were confirmed in this particle. The number of tungsten columns in this field is calculated to be 2249 columns in the field from the size of the unit lattice and the size of the field, since there are three tungsten columns in the unit lattice. In other words, in the STEM-HAADF image of the composite tungsten oxide particles of this example from the

[0001] incidence, dark areas, which are W defects, are present in 0.67% of the columns in terms of number.

[0289] In addition, in Examples 2 and 3 described later, near-infrared absorbing particle dispersions are prepared under the same conditions as in this Example, except that the diameter of the zirconia beads used in the dispersion process is changed. Since the diameter of the zirconia beads used in Examples 2 and 3 is 0.3 mm or less, the number ratio of dark areas in the composite tungsten oxide particles is almost the same as in this Example. Therefore, in Examples 2 and 3, the number ratio of dark areas in the STEM-HAADF image from

[0001] incidence for the composite tungsten oxide particles is in the range of 0.2% to 10%.

[0290] The dark areas, which are areas of low contrast, were defined as spots where the maximum Z contrast of the tungsten column spots fell to 95% or less of the average value.

[0291] Figures 10(A) to 10(F) show line profiles including W vacancies in STEM-HAADF images of the composite tungsten oxide particles in Example 1. Figures 10(A) to 10(F) respectively correspond to the line profiles at lines L1 to L6 in Figure 9(B).

[0292] Although the Z contrast may vary within the same line due to factors such as particle thickness and inclination relative to the electron beam, the maximum Z contrast values ​​of the spots of each tungsten column within the field of view were averaged to determine the Z contrast intensity of W atoms in the bulk region without W defects. The average value of the maximum Z contrast values ​​of the spots of each tungsten column within the field of view was used as the standard, and the locations where the maximum contrast value of the tungsten column spots was 95% or less of the average value were determined as W defects.

[0293] In the line L1 shown in FIG. 10(A), the maximum value of the Z contrast at point P1 is 89.1% of the average value, and at point P2 it drops to 88.4%, and these points become W-deficient portions.

[0294] On line L2 shown in FIG. 10(B), the maximum value of Z contrast decreased to 89.3%, 92.8%, 93.2%, and 91.35% of the average value at points P3 to P6, respectively.

[0295] On line L3 shown in FIG. 10C, at points P7 and P8, the maximum value of the Z contrast decreased to 86.95% and 85.6%, respectively, with respect to the average value.

[0296] On line L4 shown in FIG. 10D, at points P9 and P10, the maximum value of the Z contrast decreased to 89.2% and 89.4%, respectively, with respect to the average value.

[0297] On line L5 shown in FIG. 10(E), at point P11, the maximum value of the Z contrast decreased to 88.6% of the average value.

[0298] On line L6 shown in FIG. 10(F), at points P12 to P15, the maximum value of the Z contrast decreased to 94.0%, 93.2%, 93.4%, and 90.6% of the average value, respectively.

[0299] The transmitted light profile was measured under the above-mentioned conditions as the optical characteristics of the near infrared absorbing particle dispersion liquid according to Example 1. The results of the transmitted light profile are shown in FIG.

[0300] FIG. 14(A) shows a transmission electron microscope image of composite tungsten oxide particles, which are near-infrared absorbing particles contained in the near-infrared absorbing particle dispersion liquid. [Example 2] When the reduced particles A were dispersed to prepare a near-infrared absorbing particle dispersion, zirconia beads having a diameter of 0.1 mm were used. Except for the above, the near-infrared absorbing particle dispersion according to Example 2 was obtained by the same operation as in Example 1. The average particle diameter based on the number of the composite tungsten oxide particles contained in the near-infrared absorbing particle dispersion according to Example 2 was 10.61 nm. Other particle size characteristics are shown in Table 1.

[0301] The transmitted light profile of the near infrared absorbing particle dispersion liquid according to Example 2 is shown in FIG.

[0302] FIG. 14(B) shows a transmission electron microscope image of composite tungsten oxide particles, which are near-infrared absorbing particles contained in the near-infrared absorbing particle dispersion liquid. [Example 3] When the reduced particles A were dispersed to prepare a near infrared absorbing particle dispersion, zirconia beads having a diameter of 0.3 mm were used. Except for the above, the near infrared absorbing particle dispersion according to Example 3 was obtained by the same operation as in Example 1. The number average particle diameter of the composite tungsten oxide particles contained in the near infrared absorbing particle dispersion according to Example 3 was 18.12 nm. Other particle size characteristics are shown in Table 1.

[0303] The transmitted light profile of the near infrared absorbing particle dispersion liquid according to Example 3 is shown in FIG.

[0304] FIG. 14(C) shows a transmission electron microscope image of composite tungsten oxide particles, which are near-infrared absorbing particles contained in the near-infrared absorbing particle dispersion liquid. [Comparative Example 1] 0.216 kg of Cs2CO3 was dissolved in 0.330 kg of water, and the resulting solution was added to 1.000 kg of H2WO4 and thoroughly stirred, and then dried to obtain a dried product. The dried product was placed in an electric furnace and heated while supplying 5% H2 gas by volume with N2 gas as a carrier, and was fired at a temperature of 800°C for 1 hour. After that, the supply gas was switched to only N2 gas, and the temperature was lowered to room temperature to obtain a composite tungsten oxide coarse powder according to Comparative Example 1. The obtained coarse powder was in the form of a mass that could be visually confirmed.

[0305] Each material was weighed so that the obtained composite tungsten oxide coarse powder was 10% by mass, the dispersant a was 10% by mass, and the butyl acetate was 80% by mass. The weighed materials were placed in a paint shaker together with zirconia beads having a diameter of 0.3 mm, and a dispersion process was performed for 15 hours using the paint shaker to obtain a near-infrared absorbing particle dispersion liquid according to Comparative Example 1. The average particle size (measured by a transmission electron microscope) of the composite tungsten oxide particles in the obtained dispersion liquid according to Comparative Example 1 was measured to be 15.46 nm. Other particle size characteristics are shown in Table 1. The average particle size was measured and calculated using the same procedures and conditions as in Example 1. In addition, the dispersion liquid according to Comparative Example 1 was taken, and the solvent was removed to obtain composite tungsten oxide particles according to Comparative Example 1, Cs 0.33 WO3 particles were obtained.

[0306] 11(A) and 11(B) show the composite tungsten oxide particles according to Comparative Example 1, which are Cs 0.33 The STEM-HAADF image of a WO3 particle is shown in Figure 11(A). Figure 11(B) shows an enlarged image of a square region 111 in the particle shown in Figure 11(A). Powders synthesized via the solid-phase method have a fracture surface due to the long-term dispersion process. Since contrast is affected by the particle thickness, the region 111 in the center of the particle, where this effect is thought to be small, was enlarged and extracted.

[0307] In Figure 11(B), low contrast regions of the Cs column were confirmed at the locations indicated by arrows 112 and 113. The loss of this Cs column is thought to be the result of Cs being desorbed during the long-term crushing process.

[0308] Figures 12(B) to 12(D) show the results of extracting line profiles of lines L11 to L13, which are W / W columns, in the STEM-HAADF image shown in Figure 12(A). No point was confirmed where the Z contrast of W atoms was 95% or less of the average contrast in any location. In other words, it was confirmed that no W deficiency occurred.

[0309] The transmitted light profile was measured under the above-mentioned conditions as the optical characteristics of the near infrared absorbing particle dispersion liquid according to Comparative Example 1. The results of the transmitted light profile are shown in FIG.

[0310] FIG. 14(D) shows a transmission electron microscope image of composite tungsten oxide particles, which are near-infrared absorbing particles contained in the near-infrared absorbing particle dispersion liquid. [Table 1] [Table 2] It was confirmed that in the near-infrared absorbing particle dispersions of Examples 1 to 3 and Comparative Example 1 shown in FIG. 13 and Table 2, even if the peak transmittance in the wavelength region of 450 nm or more and 600 nm or less was set to 80% or more, the bottom of the transmittance in the near-infrared region could be made to be 10% or less.

[0311] 13 and Table 2, it was confirmed that the transmittance at wavelengths of 700 nm and 800 nm of the near-infrared absorbing particle dispersions of Examples 1 to 3 was higher than the transmittance of the near-infrared absorbing particle dispersion composed of the conventional composite tungsten oxide particles of Comparative Example 1. That is, the near-infrared absorbing particle dispersions of Examples 1 to 3 also transmit light on the long wavelength side of the visible light region (wavelengths of 380 nm or more and 780 nm or less).

[0312] Specifically, it was confirmed that the near infrared ray absorbing particle dispersion liquids of Examples 1 to 3 had a transmittance of 50% or more at a wavelength of 700 nm and a transmittance of 20% or more at a wavelength of 800 nm when the transmittance was set to 75% or more at a wavelength of 600 nm. Also, the near infrared ray absorbing particle dispersion liquids of Examples 1 to 3 had a transmittance of 15% or less at a wavelength of 1000 nm.

[0313] Therefore, the composite tungsten oxide particles of Examples 1 to 3 also transmit red light with a wavelength of about 800 nm, which shows that they also contribute to improving color tone compared to Comparative Example 1, which is a conventional composite tungsten oxide particle. [Explanation of symbols]

[0314] 10 Composite material manufacturing equipment 11 Storage area 12 Two-fluid nozzle 13 Reaction tube 131 Piping 14 Filters 15 Ejector 20 Reduction treatment equipment 21 Reaction tube 21A One side 21B Other mouth 22 Heater 23 Container 24 Composite tungsten oxide particles 30 Near infrared absorbing particle dispersion 31 Near infrared absorbing particles 32 Liquid Media 40 Near infrared absorbing particle dispersion 41 Near infrared absorbing particles 42 Solid medium 50 Near infrared absorbing laminate 51 Near infrared absorbing particle dispersion 521, 522 Transparent base material 60 Near infrared absorbing transparent substrate 61 Transparent base material 61A One side 62 Near infrared absorbing layer 701 W / W column 702 W / Cs column 71 W atoms 72 O atoms 73 M elements 74 Octahedron 75 void 91 areas L1~L6 lines P1~P15 points 111 areas 112, 113 Arrow L11~L13 lines

Claims

1. A composite tungsten oxide particle comprising a composite tungsten oxide, The composite tungsten oxide is General formula M x W y O z (wherein M element is one or more elements selected from alkali metal elements, alkaline earth metal elements, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, and I; W is tungsten; O is oxygen; 0.20≦x / y≦0.37, 2.2≦z / y≦3.3), The crystal system is hexagonal, In a STEM-HAADF image of the composite tungsten oxide particle from a [001] incidence, the composite tungsten oxide particle contains spots in which the Z contrast of tungsten atoms has dropped to 95% or less of the average value at a ratio of 0.01% to 10% by number, Composite tungsten oxide particles having a coefficient of variation of 0.2 or less, calculated by dividing the standard deviation of the number-based particle size distribution by the number-based average particle size.

2. The composite tungsten oxide particles according to claim 1 , wherein the M element includes one or more elements selected from the group consisting of Rb and Cs.

3. 3. The composite tungsten oxide particle according to claim 1, wherein the number-based average particle size is 5 nm or more and 200 nm or less.

4. Near infrared absorbing particles and a liquid medium, A near infrared absorbing particle dispersion liquid, wherein the near infrared absorbing particles are the composite tungsten oxide particles according to claim 1 or 2.

5. Near infrared absorbing particles and a solid medium, A near infrared absorbing particle dispersion, wherein the near infrared absorbing particles are the composite tungsten oxide particles according to claim 1 or 2.

Citation Information

Patent Citations

  • Potassium-cesium-tungsten bronze particles

    JP2012532822A

  • Flame spray pyrolysis with versatile precursors for metal oxide nanoparticle synthesis and applications of submicron inorganic oxide compositions for transparent electrodes

    US20100102700A1

  • Infrared shielding material microparticle dispersion, infrared shield, process for producing infrared shielding material microparticle, and infrared shielding material microparticle

    WO2005037932A1

  • Process for producing tungsten oxide and tungsten mixed oxides

    WO2017129516A1